Highly selective solar CO2 conversion into ethanol over metal-free sulfonated g-C3N4/nitrogen doped reduced graphene oxide hybrid photocatalyst - Sachin G. Ghugal; Amol U. Pawar; Park Kyoung Mo; Poonchi Sivasankaran Ramesh; Harish Reddy Inta; Sanjeev Gupta; Sung-hoon Oh; Muhammad Zaeem Azam Khan; Young Seok Son; Hyunchul Shin; Hongxian Han; Young Soo Kang (Chemical Engineering Journal, 2026)

Citric acid-driven metabolic regulation strategy for coordinating nitrogen retention and phosphorus activation in aerobic composting - Feichao Zhang; He Zhang; Han Zhang; Yuhong Wang; Anthony G. Hay; Xu He; Hong Wang; Huijiao Yao; Jian Chang; Liang Zhang; Yufang Tao (Bioresource Technology, 2026)

Examination of DNAm PhenoAge as an epigenetic biomarker for perioperative risk in adult spinal deformity surgeries - Michael P. Kelly; Jeffrey Hills; Justin S. Smith; Lawrence G. Lenke; Han Jo Kim; Shay Bess; Breton Line; Virginie Lafage; Renaud Lafage; Eric Klineberg; Ferran Pellise; Khaled Kebaish; et al. (GeroScience, 2026)

Retraction notice to “Mitigation of the mobilization and accumulation of toxic metal(loid)s in ryegrass using sodium sulfide” [Sci. Total Environ. 909 (2024) 168387] - Han Zhang; You Li; Ronghua Li; Weilong Wu; Hamada Abdelrahman; Jianxu Wang; Samir G. Al-Solaimani; Vasileios Antoniadis; Jörg Rinklebe; Sang Soo Lee; Sabry M. Shaheen; Zengqiang Zhang (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Behavioural thermoregulation segregates sick and healthy fish to enable selective treatment - Massiel F. Copara Chino; Jayoon Lee; Yujin Han; Julia G. Neyedly; Matthew L. Michnik; Patrick Whittaker; Kathryn Smith; Keith B. Tierney; Yamila Carpio; Mario P. Estrada; Mark D. Fast; Brian Dixon; et al. (Aquaculture, 2026)

Driving mechanisms and economic coupling development of agricultural net carbon sink in Chongming Island, Shanghai: a synergistic approach using LMDI-Tapio and entropy weight methods - Yuhong Wang; Hong Tao; He Zhang; Feichao Zhang; Han Zhang; Anthony G. Hay (Environmental Science and Pollution Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mosquito-borne disease among individuals experiencing homelessness in the USA: a literature review - André B. B. Wilke; Megan D. Hill; Allisandra G. Kummer; Chalmers Vasquez; John-Paul Mutebi; Xi Huo; Han Li; Jing Chen; Shigui Ruan; John C. Beier; Maria Litvinova; Thomas Byrne; et al. (Journal of Pest Science, 2026)
Mosquito-borne diseases are a major public health issue. The USA has experienced mosquito-borne disease outbreaks, including West Nile virus, Zika, dengue, and malaria, highlighting widespread risk across the country. In the USA, exposure to mosquito vectors primarily occurs outdoors. Individuals experiencing unsheltered homelessness are particularly vulnerable to mosquito-borne diseases due to their increased exposure to mosquito vectors, limited access to healthcare, and high prevalence of underlying conditions. This review aims to examine the literature on mosquito-borne disease infections among individuals experiencing homelessness in the USA between 1999 and 2024. Our search strategy used Boolean methods on PubMed, Scopus, and Web of Science to select relevant publications. Two queries were used: the first query focused on individuals experiencing homelessness and mosquito-borne diseases, and the second one focused on epidemiological analyses of mosquito-borne disease outbreaks in the USA. Only studies reporting at least one infection among individuals experiencing homelessness were included. Our search resulted in the identification of 347 studies. After screening them, eight were ultimately included in this review. Half of the studies identified West Nile virus among individuals experiencing homelessness, and the other half reported cases of malaria. These studies show that individuals who spend more time outdoors, including individuals experiencing homelessness, may be at a greater risk of MBDs compared to the general population. However, the full extent of mosquito-borne disease exposure among individuals experiencing homelessness remains unclear. With climate change and globalization, there is a consensus in the literature showing an increasing risk of mosquito-borne disease transmission in the next decades, and we have already started to witness this increasing trend. Moreover, the USA is experiencing a steep increase in the overall nationwide homeless population. Therefore, we argue that developing policies aimed at providing homeless populations with housing during mosquito-borne disease outbreaks could be instrumental in protecting this segment of the population and promoting health equity.

Carbon tax/subsidy and the potential for forest carbon sinks in China - Han Zhang; G. Cornelis van Kooten; Chao Yue; Hongqiang Yang; Peter Smith (European Journal of Forest Research, 2026)
China seeks to expand forest-based carbon sinks, yet it remains unclear which pricing instruments and price levels deliver the largest additional sequestration under China’s land and governance constraints. We develop an evaluative framework that separates the extensive and intensive margins by pairing a province-level land-use share model for the extensive margin with a rotation model for the intensive margin, and benchmark all results against a dynamic business-as-usual projection (2020–2060). We compare three instruments—tax-only, subsidy-only, and hybrid (tax-and-subsidy)—across carbon prices. Four results emerge. First, while the hybrid consistently produces the largest sink, its advantage over a subsidy-only policy is small (≈ 1.08–9.38%), making subsidy-only the practical second-best once administrative/transaction costs of the tax leg are considered. Second, policy responses are non-monotonic in the price signal: a low-efficiency band exists around 200–300 CNY/tCO 2 , whereas the carbon price of 100 CNY/tCO 2 delivers the second-highest sink at the lowest average cost, making it the cost-effective choice in our setting. Third, policy effectiveness in China is transmitted primarily through the intensive margin: most additional sinks arise from longer rotations and higher stand densities on existing forests, not from large net area gains. Fourth, a tax-only instrument risks a “carbon-tax trap”: the harvest tax has little leverage on rotations but depresses forestland rent, yielding net area losses and a negative total effect. These findings provide useful evidence for policy-making to incentivize forest carbon sequestration in China.

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

Geothermal resource identification in Australia using shallow groundwater temperature data - Y. Han; L. T. White; W. G. P. Kumari; T. Murray (Australian Journal of Earth Sciences, 2026)

Machine-learning-enabled starch/MXene moisture sensing bioelectronics for human monitoring and interaction - Ming Dong; Yansong Li; Subash Rai; Han Zhang; Emiliano Bilotti; Dimitrios G. Papageorgiou (Chemical Engineering Journal, 2026)

How does the built environment affect obesity? A review from the perspective of urban planning - H. Wu; G. Han; L. Yang; R. Liang (International Journal of Environmental Science and Technology, 2026)

Chemical characterization of non-polar organic compounds transported by methane ebullition in an oil sands pit lake - Han Bao; Chenlu Wang; Kevin G. Mumford; Greg F. Slater (Journal of Environmental Management, 2026)

Assessing the effectiveness of SDGs implementation in reducing intra-urban spatial inequality: A spatiotemporal heterogeneous modeling in China - Weishi Zhang; Yitong Han; David G. Streets; Can Wang; Ying Xu (Environmental Impact Assessment Review, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dissolved organic matter dynamics in a whale-dominated coastal system: Insights from Península Valdés, Argentina - Luis G. Egea; Rocío Jiménez-Ramos; Valeria C. D'Agostino; Mariana Degrati; Sebastián Giacomino; Guebuem Kim; Heejun Han; Rocío Loizaga (Marine Environmental Research, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

Contrasting effects of long-term nitrogen and phosphorus fertilization on phosphorus availability in soil - Ran Tong; Han Yu; Nianfu Zhu; Yongzhao Miao; Song Chen; Yeshi Zheng; Tonggui Wu; G. Geoff Wang; Yakov Kuzyakov (Soil Ecology Letters, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

Syngas production from biomass pyrolysis followed by in-line biochar-catalytic reforming: the effect of space velocity, particle size, and morphology - Hanmin Yang; Yazhe Wang; Yanghao Jin; José Juan Bolívar Caballero; Shiwei Chen; Ziyi Shi; Tong Han; Linda Sandström; Pär G. Jönsson; Weihong Yang (Biomass and Bioenergy, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

The influential mechanisms of digital infrastructure construction on green development in China- A quasi-DID and heterogeneity analysis - Han Bu; Weishi Zhang; Xin Pei; David G. Streets (Environment, Development and Sustainability, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Strongest untreated mycelium materials produced by Schizophyllum commune dikaryons - Antonio d’Errico; Jeroen G. van den Brandhof; Anna Bogomolova; Han A. B. Wösten (World Journal of Microbiology and Biotechnology, 2025)
Monokaryons of Schizophyllum commune are preferred to produce mycelium materials due to their inability to form fruiting bodies and thereby producing uniform materials. However, a single gene mutation in such monokaryons can negatively impact biomass, chemical composition, and mechanical properties of the mycelium material. Dikaryons contain two instead of a single nucleus per hyphal compartment, thereby promoting higher phenotypic stability in the case of recessive mutations. Here, biomass formation and mycelium material properties of four S. commune dikaryons were compared to a monokaryon commonly used in mycelium material production. To this end, mycelium was grown in three different growth media. The monokaryon yielded a biomass of 3.11–9.31 g L −1 , an ultimate tensile strength ( σ ) of 4.62–7.77 MPa, a Young’s modulus ( E ) of 0.38–0.64 GPa, and an elongation at break ( ε ) of 1.51–1.93%. Most dikaryons exhibited a strikingly higher σ (19.55–47.29 MPa), a similar or higher E (0.69–2.06 GPa) and ε (2.09–7.92%), and a lower or similar biomass (1.48–7.71 g L −1 ). Notably, σ values up to 47.29 and 47.16 MPa were obtained for the diakaryotic S. commune strains 139 and 351, respectively, making them the strongest untreated mycelium materials reported so far. Results suggest that this high strength is caused, at least in part, by a high amount of KOH-soluble cell wall components and by low sc3 expression.

Whole Genome Sequencing Reveals How Plasticity and Genetic Differentiation Underlie Sympatric Morphs of Arctic Charr - Khrystyna Kurta; Mariano Olivera Fedi; Kendall Baker; Tom Barker; Leah Catchpole; Claudio Ciofi; Arianna Cocco; Joanna Collins; Genevieve Diedericks; Maria Angela Diroma; Alex Durrant; Kjetil Hindar; et al. (Molecular Ecology, 2025)
Salmonids have a remarkable ability to form sympatric morphs after postglacial colonisation of freshwater lakes. These morphs often differ in morphology, feeding and spawning behaviour. Here, we explored the genetic basis of morph differentiation in Arctic charr ( n = 283) by first establishing a high‐quality reference genome and then using this in whole genome sequencing of distinct morphs present in two Norwegian and two Icelandic lakes. The four lakes represent the spectrum of genetic differentiation between morphs from one lake with no genetic differentiation between morphs, implying phenotypic plasticity, to two lakes with locus‐specific genetic differentiation, implying incomplete reproductive isolation, and one lake with strong genome‐wide divergence consistent with complete reproductive isolation. As many as 12 putative inversions ranging from 0.45 to 3.25 Mbp in size segregated among the four morphs present in one lake, Thingvallavatn, and these contributed significantly to the genetic differentiation among morphs. None of the putative inversions were found in any of the other lakes, but there were cases of partial haplotype sharing in similar morph contrasts in other lakes. Our findings are consistent with a highly polygenic basis of morph differentiation with population‐specific selection on alleles linked to the development of similar morph phenotypes. The results support a model where morph differentiation is first established through phenotypic plasticity, leading to niche expansion and separation. This may be followed by gradual development of reproductive isolation, locus‐specific differentiation and eventually complete reproductive isolation and genome‐wide divergence.

P29-12 Four-Week Repeated Inhalation Toxicity Study of SiO2-ZnO Mixed Nanoparticles in Sprague-Dawley Rats - Y.-J. Heo; M.-J. Yang; H.-Y. Han; H.J. Jin; G.J. Oh; G.-H. Bae; M.-K. Song (Toxicology Letters, 2025)

P27-07 What Does “Success” Look Like in Compliance Check Decisions by the European Chemicals Agency? The Curious Cases of Accepted Read-Across Adaptations - H.M. Roe; H.-H.D. Tsai; N. Ball; G. Han; W.A. Chiu; I. Rusyn (Toxicology Letters, 2025)

Surfactant-assisted colloidal size and charge control in perovskite solutions for high-performance and stable solar cells - Gyeong G. Jeon; Sang Eun Yoon; Jonghoon Han; Hye W. Chun; So Jeong Shin; Min Jun Choi; Sang Uk Park; Seo-Jin Ko; Shujuan Huang; Nochang Park; Jong H. Kim; Jincheol Kim (Chemical Engineering Journal, 2025)

Characterization of pure mycelium materials from different mushroom-forming fungi - Jeroen G. van den Brandhof; Noortje Hansen; Chen Hou; Sander C. Broers; Martin Tegelaar; Han A. B. Wösten (Antonie van Leeuwenhoek, 2025)
Pure mycelium materials (PMMs) are a sustainable alternative for a range of non-sustainable products such as textile, leather and meat. So far, properties of PMMs of different fungi have not been systematically assessed. Here, 11 mushroom-forming fungi, of which 10 isolated from nature, were grown in liquid shaken cultures. Schizophyllum commune, Ganoderma resinaceum , and Trametes betulina produced the highest biomass (8.62, 7.58, and 6.94 g L −1 , respectively) when grown as mono-cultures in malt extract broth. Therefore, PMM properties were determined of mono-cultures, mixed-cultures, and co-cultures of these three fungi. The maximum tensile strength of the PMMs of the mono-cultures, mixed-cultures, and co-cultures of S. commune , G. resinaceum , and T. betulina did not show significant differences and ranged between 4.5 to 6.3 MPa. The elongation at break of the different PMMs was generally low and ranged between 0.8 and 1.6%. The Young’s modulus of the PMMs also showed relatively small differences ranging between 408 and 710 MPa. The G. resinaceum PMMs showed the lowest water uptake, while the S. commune mono-, mixed- and co-culture PMMs showed the highest water contact angle. Together, it is concluded that the properties of the mono-, mixed-, and co-cultures of S. commune , G. resinaceum , and T. betulina are not very different. These data suggest that the species of mushroom forming fungi does not have a major impact on PMM properties of biomass from liquid shaken cultures.

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Expression of progerin enhances disease-related endpoints in a tau seeding reporter cell system - Zhuang Zhuang Han; Sang-Gyun Kang; Erik Gomez-Cardona; Serene Wohlgemuth; Klinton Shmeit; Luis Arce; Jiri G. Safar; Olivier Julien; David Westaway (GeroScience, 2025)
Sporadic Alzheimer’s disease and some forms of frontotemporal lobar degeneration (FTLD-tau) are neurological disorders of later life where cognitive deficits follow from the progressive accumulation of microtubule-associated tau protein. Disease-related tau accumulation is marked by altered subcellular distribution and rearrangement of this natively unstructured protein into alternative conformational forms, including highly organized fibrillar assemblies. With a partial analogy to effects seen in prion diseases, pathological tau conformers have a templating activity called seeding that may be measured in cellular and cell-free systems. Moreover, cellular systems and disease models can recapitulate “strain effects” wherein the same tau amino acid sequence can adopt markedly different conformations. Here we analyzed FTLD-tau conformers in cellular reporter systems expressing a pro-aging mutant form of the lamin A protein termed “progerin.” Measured versus the baseline performance of a reporter system based on HEK293 cells, the addition of tau burden or progerin expression produced only mild changes in proteomic analyses or morphology, whereas application of both stressors produced a notable shift in ER stress and homeostasis, including increased levels of DNAJC10 and DNAJA2. The phenotypic effects scored here appear unrelated to the generation of new tau strains or to the type of strain input, insofar as progerin-expressing cells were more responsive to tau seeding by diverse brain samples containing different populations of tau conformers. Thus, premature aging and disease-associated tau conformers can exhibit an additive relationship in a model system.

Calcium hydroxide dissolution rates: Dependence on temperature and saturation - Yoonjung Han; Mine G. Ucak-Astarlioglu; Jedadiah F. Burroughs; Jeffrey W. Bullard (Chemical Engineering Journal, 2025)

Diluted swine and aquaculture wastewater enhance carbon sequestration and nutrient removal by the red seaweed Agardhiella subulata - W.Sanjaya Weerakkody; Hsueh-Han Hsieh; Vicente G Abedneko; Ka Hin Ling; Tzu-Chieh Chung; Zih-Yi Wang; Yung-Yen Shih; Tse-Min Lee; Chen Xu; Peter H. Santschi; Chin-Chang Hung (Bioresource Technology, 2025)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Isolation and characterization of microcrystalline cellulose from rice stalk agro-waste and its application in enhancing inherent properties of PBAT biofilm - Gokulkumar Sivanantham; Divya Divakaran; Indran Suyambulingam; G. Suganya Priyadharshini; Yamuna Munusamy; Adhigan Murali; Sung Soo Han (Process Safety and Environmental Protection, 2025)

How does clean heating policy affect employment in local and neighbouring cities: Spatial quasi-experimental evidence from China - Weishi Zhang; Ying Xu; Han Bu; David G. Streets; Can Wang (Journal of Cleaner Production, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

An Intermittent Fasting Intervention for Black Adults Can Be Feasibly Implemented in Black Churches: A Cluster Randomized Controlled Pilot Study - Karen H. Kim Yeary; Detric Johnson; Narseary Harris; Han Yu; Frances G. Saad-Harfouche; Cassy Dauphin; Elizabeth DiCarlo; Tessa Flores; Song Yao; Krista Varady; Li Tang (Journal of the Academy of Nutrition and Dietetics, 2025)

Carbon sink potential and the cost of afforestation in northwest China when accounting for ecosystem service value - Han Zhang; G. Cornelis van Kooten; Chao Yue; Zongshun Wang (Journal of Environmental Management, 2025)

Excitation functions for fast neutron induced reactions on Al, Zr, In and Au - B. Liu; G. Tian; R. Han; F. Shi; H. Sun; Z. Chen; Z. Zhang; Q. Li; P. Luo (Annals of Nuclear Energy, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

What dominates the variation of ecosystem services across different urban expansion patterns?—Evidence from the Yangtze River Delta region, China - Dan Yi; Jie Guo; Steven G. Pueppke; Yi Han; Guanqiao Ding; Minghao Ou; Eric Koomen (Environmental Impact Assessment Review, 2025)

Development of Zinc-Containing Chitosan/Gelatin Coatings with Immunomodulatory Effect for Soft Tissue Sealing around Dental Implants - Jing Han; Jorine G. F. Sanders; Lea Andrée; Bart A. J. A. van Oirschot; Adelina S. Plachokova; Jeroen J. J. P. van den Beucken; Sander C. G. Leeuwenburgh; Fang Yang (Tissue Engineering and Regenerative Medicine, 2025)
BACKGROUND: Soft tissue integration (STI) around dental implant abutments is a prerequisite to prevent bacterial invasion and achieve successful dental implant rehabilitation. However, peri-implant STI is a major challenge after dental abutment placement due to alterations in the immune microenvironment upon surgical dental implant installation. METHODS: Based on known immunomodulatory effects of zinc, we herein deposited zinc/chitosan/gelatin (Zn/CS/Gel) coatings onto titanium substrates to study their effect on macrophages. First, we exposed macrophages to cell culture media containing different zinc ion (Zn 2+ ) concentrations. Next, we explored the immunomodulatory effect of Zn/CS/Gel coatings prepared via facile electrophoretic deposition (EPD). RESULTS: We found that Zn 2+ effectively altered the secretome by reducing the secretion of pro-inflammatory and enhancing pro-regenerative cytokine secretion, particularly at a Zn 2+ supplementation of approximately 37.5 μM. Zn/CS/Gel coatings released Zn 2+ in a concentration range which effectively stimulated pro-regenerative macrophage polarization as demonstrated by M2 macrophage polarization. Additionally, the impact of these Zn 2+ -exposed macrophages on gingival fibroblasts incubated in conditioned medium showed stimulated adhesion, proliferation, and collagen secretion. CONCLUSION: Our promising results suggest that controlled release of Zn 2+ from Zn/CS/Gel coatings could be applied to immunomodulate peri-implant STI, and to enhance dental implant survival.

Branched-chain amino acids and their metabolites decrease human and rat hepatic stellate cell activation - Maria Camila Trillos-Almanza; Magnolia Martinez Aguilar; Manon Buist-Homan; Nils Bomer; Karla Arevalo Gomez; Vincent E. de Meijer; Frederike G. I. van Vilsteren; Hans Blokzijl; Han Moshage (Molecular Biology Reports, 2024)
Background End-stage liver diseases (ESLDs) are a significant global health challenge due to their high prevalence and severe health impacts. Despite the severe outcomes associated with ESLDs, therapeutic options remain limited. Targeting the activation of hepatic stellate cells (HSCs), key drivers of extracellular matrix accumulation during liver injury presents a novel therapeutic approach. In ESLDs patients, branched-chain amino acids (BCAAs, leucine, isoleucine and valine) levels are decreased, and supplementation has been proposed to attenuate liver fibrosis and improve regeneration. However, their effects on HSCs require further investigation. Objective To evaluate the efficacy of BCAAs and their metabolites, branched-chain α-keto acids (BCKAs), in modulating HSCs activation in human and rat models. Methods Primary HSCs from rats and cirrhotic and non-cirrhotic human livers, were cultured and treated with BCAAs or BCKAs to assess their effects on both preventing (from day 1 of isolation) and reversing (from day 7 of isolation) HSCs activation. Results In rat HSCs, leucine and BCKAs significantly reduced fibrotic markers and cell proliferation. In human HSCs, the metabolite of isoleucine decreased cell proliferation around 85% and increased the expression of branched-chain ketoacid dehydrogenase. The other metabolites also showed antifibrotic effects in HSCs from non-cirrhotic human livers. Conclusion BCAAs and their respective metabolites inhibit HSC activation with species-specific responses. Further research is needed to understand how BCAAs influence liver fibrogenesis. BCKAs supplementation could be a strategic approach for managing ESLDs, considering the nutritional status and amino acid profiles of patients. Graphical abstract The antifibrotic effects of BCAAs and BCKAs in various conditions are depicted for human HSCs (left) and rat HSCs (right) The symbol ‘↓’ indicates a downregulation or a decrease. α-SMA alpha-smooth muscle actin, BCAAs branched-chain amino acids, BCKAs branched-chain keto acids, HSCs hepatic stellate cells, KMV α-keto-β-methylvalerate. Figure created with Biorender.com

Correction to: Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; Jonas De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Fetal weight growth trajectories and childhood development: A population-based cohort study - Xinmei Chen; Hongxiu Liu; Aifen Zhou; Feng Jin; Chufeng Jing; Yuanyuan Li; Wei Xia; Linda G. Kahn; Ya Xie; Xingliang Xiang; Shuting Cao; Wenxin Zhang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Reassessing early to mid-Neoproterozoic (∼885–720 Ma) tectonic evolution of the southwestern Jiangnan Orogen: A detrital zircon perspective - Yong Liang; Han Zheng; Zhiyuan He; Johan De Grave; Huan Li; Zongyuan Tang; Gary G. Lash; Peixuan Kang (Precambrian Research, 2024)

Using stable isotopes to inform water resource management in forested and agricultural ecosystems - Francesca Scandellari; Taha Attou; Adrià Barbeta; Fabian Bernhard; Concetta D’Amato; Katya Dimitrova-Petrova; Amanda Donaldson; Oludare Durodola; Stefano Ferraris; Marius G. Floriancic; Gabriela Fontenla-Razzetto; Malkin Gerchow; et al. (Journal of Environmental Management, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Investigation of changes in the fine structure of sorghum starch in the baijiu fermentation process - Chuantian Yang; Peng Lv; Huaxin Han; Xue Xiao; Chen Xu; Robert G. Gilbert; Enpeng Li (Food Hydrocolloids, 2024)

Oxygen supersaturation adds resistance to a cnidarian: Symbiodiniaceae holobiont under moderate warming in experimental settings - Silvia Arossa; Shannon G. Klein; Elisa Garuglieri; Alexandra Steckbauer; Anieka J. Parry; Jacqueline V. Alva Garcia; Taiba Alamoudi; Xinyuan Yang; Shiou-Han Hung; Octavio R. Salazar; Ramona Marasco; Marco Fusi; et al. (Frontiers in Marine Science, 2024)
Ocean warming reduces O 2 solubility and increases organismal O 2 demand, endangering marine life. Coastal ecosystems, however, experience O 2 supersaturation during peak daytime temperatures due to metabolic cycles. Recent discoveries show that this environmental supersaturation can reduce the vulnerability of tropical species to warming by satisfying their oxygen requirements. To test whether this also occurs within the cnidarian holobiont, we elevated internal O 2 in Cassiopea andromeda at nighttime (i.e. holobiont respiration prevails on Symbiodniaceae O 2 production) relying on bell pulsation for ventilation, then experimentally subjected them to thermal stress (+1°C day -1 ). Though ecologically unrealistic, this approach verified our hypothesis and eliminated confounding factors. Holobionts were exposed to either constant levels of 100% air saturation (100AS) or nighttime supersaturation (NSS; where 100% air saturation transitioned to O 2 supersaturation at nighttime). At sublethal temperatures, supersaturation mitigated reductions in holobiont size of ~ 10.37% (-33.418% ± 0.345 under 100AS vs -23.039% ± 0.687 under NSS). Supersaturation alleviated chlorophyll- a loss by 42.73% until 34°C, when counteraction of this process could not be sustained due to excessive thermal stress. Supersaturation also enriched potentially beneficial bacterial taxa of the microbiome and selected a more consistent bacterial community. Although modest, the detected effects show that a O 2 surplus increased the resistance of the holobionts to thermal stress.

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Sustainability information, taste perception and willingness to pay: The case of bird-friendly coffee - Klaus G. Grunert; Han-Seok Seo; Di Fang; Victoria J. Hogan; Rodolfo M. Nayga Jr. (Food Quality and Preference, 2024)

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Optimizing cultivation strategies and scaling up for fucoxanthin production using Pavlova sp. - Chun-Yen Chen; Ping-Yung Liu; Yu-Han Chang; Dillirani Nagarajan; Mary Joy D. Latagan; Mark Daniel G. de Luna; Jih-Heng Chen; Jo-Shu Chang (Bioresource Technology, 2024)

A natural mutant kumquat fruit with abnormal oil glands shows lower volatile production, better fruit flavor and higher resistance to postharvest disease - Man Zhu; Yang Wang; Zhebin Zeng; Xi Wu; Jiacheng Teng; Jingzong Zhang; Qianrong Han; Qiaoli Ma; Chuanwu Chen; Yunjiang Cheng; Xiuxin Deng; Niels J. Nieuwenhuizen; et al. (Postharvest Biology and Technology, 2024)

Rigid amine-incorporated silica aerogel for highly efficient CO2 capture and heavy metal removal - Haryeong Choi; Hyug Hee Han; Vinayak G. Parale; Taehee Kim; Wanje Park; Younghun Kim; Jiseung Kim; Yujin Choi; Youn-Sang Bae; Hyung-Ho Park (Chemical Engineering Journal, 2024)

Molybdenum inhibited the growth of Phytophthora nicotiana and improved the resistance of Nicotiana tabacum L. against tobacco black shank - Bingjie Yu; Junling Li; Mohamed G. Moussa; Wenchao Wang; Shaosen Song; Zicheng Xu; Huifang Shao; Wuxing Huang; Yongxia Yang; Dan Han; Bingjun Dang; Jiayang Xu; et al. (Pesticide Biochemistry and Physiology, 2024)

Geospatial liquefaction probability models based on sand boils occurred during the 2017 M5.5 Pohang, South Korea, earthquake - Hwanwoo Seo; Han-Saem Kim; Laurie G. Baise; Byungmin Kim (Engineering Geology, 2024)

Effectiveness and potential mechanism of hydrothermal modification of attapulgite for cadmium passivation in soil - G. Ma; J. Ren; L. Tao; X. Han; C. Liao; Y. Zhou; J. Ding; Y. Zhou; K. Bi (International Journal of Environmental Science and Technology, 2024)

Forecasting environmental water availability of lakes using temporal fusion transformer: case studies of China’s two largest freshwater lakes - Feng Huang; Carlos G. Ochoa; Qiongfang Li; Xingzhi Shen; Zhan Qian; Shuai Han; Nan Zhang; Meixiu Yu (Environmental Monitoring and Assessment, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

RETRACTED: Mitigation of the mobilization and accumulation of toxic metal(loid)s in ryegrass using sodium sulfide - Han Zhang; You Li; Ronghua Li; Weilong Wu; Hamada Abdelrahman; Jianxu Wang; Samir G. Al-Solaimani; Vasileios Antoniadis; Jörg Rinklebe; Sang Soo Lee; Sabry M. Shaheen; Zengqiang Zhang (Science of The Total Environment, 2024)

Effects of polyphenol-rich grape seed and green tea extracts on the physicochemical properties of 3D-printed edible soy protein films - Safoura Ahmadzadeh; Navam Hettiarachchy; Kaushik Luthra; Jingyi Chen; Han-Seok Seo; Griffiths G. Atungulu; Ali Ubeyitogullari (Food Packaging and Shelf Life, 2023)

Optimization of A2O–MBR–BAF–O3 combination process for domestic wastewater - L. Huang; J. Han; G. Wang; Y. Hou; Z. Li; F. Yi (International Journal of Environmental Science and Technology, 2023)

Quartz types and origins of the Upper Permian Dalong Formation shale of the Sichuan Basin: Implications for pore preservation in deep shale reservoirs - Ping Gao; Xianming Xiao; Guangming Meng; Gary G. Lash; Shuangjian Li; Yueqing Han (Marine and Petroleum Geology, 2023)

Surrogate modeling and global sensitivity analysis for the simultaneous growth of multiple hydraulic fractures - Shaoyi Cheng; Bisheng Wu; Ming Zhang; Xi Zhang; Yanhui Han; Robert G. Jeffrey (Computers and Geotechnics, 2023)

Afforestation triggers water mining and a single pulse of water for carbon trade-off in deep soil - Huijie Li; Han Li; Qifan Wu; Bingcheng Si; Esteban G. Jobbágy; Jeffrey J. McDonnell (Agriculture, Ecosystems & Environment, 2023)

Effect of fruiting-related genes on the formation of volatile organic compounds in the mushroom Schizophyllum commune - Axel Orban; Lisa Janaina Schwab; Luis G. Lugones; Han A. B. Wösten; Martin Rühl (Mycological Progress, 2023)
In fungi, little is known about connections between volatile organic compound (VOC) formation and developmental stages that are amongst others triggered by fruiting-related genes (FRGs). We analysed the volatilomes of Schizophyllum commune during different developmental stages in a variety of FRG-deletion strains and wild-type strains. The deletion strains Δ tea1 Δ tea1 , Δ wc-2 Δ wc-2 and Δ hom2 Δ hom2 were unable to develop fruiting bodies, and Δ fst4 Δ fst4 formed only rudimentary fruiting body structures. Early developmental stages of these strains were dominated by esters, including methyl 2-methylbutanoate, ethyl 2-methylbutanoate, isobutyl 2-methylpropionate, and 2-methylbutyl acetate, of which the last three were not found in the headspace (HS) of the wild-type samples. Compared to the wild type, in the HS of hom2 con samples, that are able to form fruiting bodies, methyl 2-methylbutanoate was the most abundant substance at early stages (68–81% of the total peak area). In contrast to fruiting body forming strains, Δ tea1 Δ tea1 , Δ wc-2 Δ wc-2 , Δ hom2 Δ hom2 and Δ fst4 Δ fst4 showed less sesquiterpenes in the HS. However, the sesquiterpenes found in the HS of FRG-deletion strains, namely, ( E )-nerolidol, δ-cadinene, L-calamenene, α-bisabolol and β-bisabolene, were not present in hom2 con or wild-type strains that mainly formed fruiting bodies and barely mycelium. Several sesquiterpenes, including α-guaiene, chamigrene and γ-gurjunene, were only found in presence of fruiting bodies. Our results show remarkable connections between FRGs, fruiting body development and VOC production in S. commune , especially counting for sesquiterpenes. Future studies are needed to reveal whether FRGs directly regulates VOC formation or indirectly by changing the phenotype.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Fellowship of the Spring: An initiative to document and protect the world's oases - Roderick J. Fensham; Rouhollah Adinehvand; Sally Babidge; Marco Cantonati; Matthew Currell; Linda Daniele; Alper Elci; Diana M.P. Galassi; África de la Hera Portillo; Salah Hamad; Dongmei Han; Hussain Ali Jawadi; et al. (Science of The Total Environment, 2023)

Corrigendum to “Carbon capture by macroalgae Sarcodia suae using aquaculture wastewater and solar energy for cooling in subtropical regions” [Sci. Total Environ. 855 (2023) 158850] - W. Sanjaya Weerakkody; Ka Hin Ling; Hsueh-Han Hsieh; Vicente G. Abedneko; Jeng-Feng Shyu; Tse-Min Lee; Yung-Yen Shih; R.R.M.K.P. Ranatunga; Peter H. Santschi; Chin-Chang Hung (Science of The Total Environment, 2023)

An integrated watershed-scale framework to model nitrogen transport and transformations - Han Qiu; Jie Niu; Dean G. Baas; Mantha S. Phanikumar (Science of The Total Environment, 2023)

SARS-CoV-2 3CL-protease inhibitors derived from ML300: investigation of P1 and replacements of the 1,2,3-benzotriazole - Alice Hooper; Jonathan D. Macdonald; Brenna Reilly; Joshua Maw; Aidan P. Wirrick; Sang Hoon Han; A. Abigail Lindsey; Emma G. Rico; Todd Romigh; Christopher M. Goins; Nancy S. Wang; Shaun R. Stauffer (Medicinal Chemistry Research, 2023)

Carbon and H2 recoveries from plastic waste by using a metal-free porous biocarbon catalyst - Yanghao Jin; Hanmin Yang; Shuo Guo; Ziyi Shi; Tong Han; Ritambhara Gond; Pär G. Jönsson; Weihong Yang (Journal of Cleaner Production, 2023)

Recent trends in management strategies for two major maize borers: Ostrinia nubilalis and Sesamia nonagrioides - Gülay Kaçar; Ana Butrón; Dimitrios Kontogiannatos; Peng Han; Maria Fernanda G. V. Peñaflor; Gema P. Farinós; Fangneng Huang; William D. Hutchison; Bruno H. S. de Souza; Rosa Ana Malvar; Anna Kourti; Ricardo Ramirez-Romero; et al. (Journal of Pest Science, 2023)

An assessment model for mapping the susceptibility of deposits accumulation on insulators driven by remotely sensed data - G. Wen; G. Han; F. Zhou; L. Shen; Y. Ma; G. Qian; H. Pan; P. Kong; J. Luo (International Journal of Environmental Science and Technology, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Global patterns and drivers of leaf photosynthetic capacity: The relative importance of environmental factors and evolutionary history - Zhengbing Yan; Jordi Sardans; Josep Peñuelas; Matteo Detto; Nicholas G. Smith; Han Wang; Lulu Guo; Alice C. Hughes; Zhengfei Guo; Calvin K. F. Lee; Lingli Liu; Jin Wu (Global Ecology and Biogeography, 2023)
Aim Understanding the considerable variability and drivers of global leaf photosynthetic capacity [indicated by the maximum carboxylation rate standardized to 25°C ( V c,max25 )] is an essential step for accurate modelling of terrestrial plant photosynthesis and carbon uptake under climate change. Although current environmental conditions have often been connected with empirical and theoretical models to explain global V c,max25 variability through acclimatization and adaptation, long‐term evolutionary history has largely been neglected, but might also explicitly play a role in shaping the V c,max25 variability. Location Global. Time period Contemporary. Major taxa studied Terrestrial plants. Methods We compiled a geographically comprehensive global dataset of V c,max25 for C 3 plants ( n = 6917 observations from 2157 species and 425 sites covering all major biomes world‐wide), explored the biogeographical and phylogenetic patterns of V c,max25 , and quantified the relative importance of current environmental factors and evolutionary history in driving global V c,max25 variability. Results We found that V c,max25 differed across different biomes, with higher mean values in relatively drier regions, and across different life‐forms, with higher mean values in non‐woody relative to woody plants and in legumes relative to non‐leguminous plants. The values of V c,max25 displayed a significant phylogenetic signal and diverged in a contrasting manner across phylogenetic groups, with a significant trend along the evolutionary axis towards a higher V c,max25 in more modern clades. A Bayesian phylogenetic linear mixed model revealed that evolutionary history (indicated by phylogeny and species) explained nearly 3‐fold more of the variation in global V c,max25 than present‐day environment (53 vs. 18%). Main conclusions These findings contribute to a comprehensive assessment of the patterns and drivers of global V c,max25 variability, highlighting the importance of evolutionary history in driving global V c,max25 variability, hence terrestrial plant photosynthesis.

The effects of dietary myo-inositol on growth and physiological, biochemical, and molecular responses in the Pacific white shrimp Litopenaeus vannamei - Qiuran Yu; Fenglu Han; Maoxian Huang; Xiaodan Wang; Jian G. Qin; Liqiao Chen; Erchao Li (Aquaculture, 2023)

Ultrathin membrane with robust and superior CO2 permeance by precision control of multilayer structures - Hoseong Han; Joel M.P. Scofield; Paul A. Gurr; Paul A. Webley; Greg G. Qiao (Chemical Engineering Journal, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Correction: Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Highly charged solar evaporator toward sustainable energy transition for in-situ freshwater & power generation - Muhammad Sultan Irshad; Yabin Hao; Naila Arshad; Muneerah Alomar; Liangyou Lin; Xiuqiang Li; Swelm. Wageh; Omar A. Al-Hartomy; Abdullah G. Al-Sehemi; Van-Duong Dao; Hao Wang; Xianbao Wang; et al. (Chemical Engineering Journal, 2023)

Sustained power output from an algal biophotovoltaic (BPV) platform using selected marine and freshwater microalgae - Cheng-Han Thong; Fong-Lee Ng; Vengadesh Periasamy; Wan Jeffrey Basirun; G. Gnana Kumar; Siew-Moi Phang (Journal of Applied Phycology, 2023)

Carbon capture by macroalgae Sarcodia suae using aquaculture wastewater and solar energy for cooling in subtropical regions - W. Sanjaya Weerakkody; Ka Hin Ling; Hsueh-Han Hsieh; Vicente G. Abedneko; Jeng-Feng Shyu; Tse-Min Lee; Yung-Yen Shih; R.R.M.K.P. Ranatunga; Peter H. Santschi; Chin-Chang Hung (Science of The Total Environment, 2023)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Integrative epigenomic and transcriptomic analyses reveal metabolic switching by intermittent fasting in brain - Gavin Yong-Quan Ng; Dominic Paul Lee Kok Sheng; Han-Gyu Bae; Sung Wook Kang; David Yang-Wei Fann; Jinsu Park; Joonki Kim; Asfa Alli-Shaik; Jeongmi Lee; Eunae Kim; Sunyoung Park; Jeung-Whan Han; et al. (GeroScience, 2022)

An Exploratory Survey on the Care for Ataxic Patients in the American Continents and the Caribbean - Laura Bannach Jardim; Ali Hasan; Sheng-han Kuo; Jonathan Javier Magaña; Marcondes França; Wilson Marques; Claudia Camejo; Luiz Carlos Santana-da-Silva; Emília Embiruçu Leão; Gisele Espíndola; Francisca Canals; Marcelo Miranda; et al. (The Cerebellum, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Sexual differences in gas exchange and chlorophyll fluorescence of Torreya grandis under drought stress - Jinwen Wang; Yang Liu; Yanxia Xu; Wenjing Chen; Yini Han; G. Geoff Wang; Songheng Jin (Trees, 2022)

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

Essential Tremor versus “ET-plus”: A Detailed Postmortem Study of Cerebellar Pathology - John T. Gionco; Whitney G. Hartstone; Regina T. Martuscello; Sheng-Han Kuo; Phyllis L. Faust; Elan D. Louis (The Cerebellum, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Novel 1,2,4-triazole analogues as mushroom tyrosinase inhibitors: synthesis, kinetic mechanism, cytotoxicity and computational studies - Balasaheb D. Vanjare; Prasad G. Mahajan; Nilam C. Dige; Hussain Raza; Mubashir Hassan; Yohan Han; Song Ja Kim; Sung-Yum Seo; Ki Hwan Lee (Molecular Diversity, 2021)

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

The Internal Microenvironment of the Symbiotic Jellyfish Cassiopea sp. From the Red Sea - Silvia Arossa; Alan Barozzi; Matteo Callegari; Shannon G. Klein; Anieka J. Parry; Shiou-Han Hung; Alexandra Steckbauer; Manuel Aranda; Daniele Daffonchio; Carlos M. Duarte (Frontiers in Marine Science, 2021)
The characterization of the internal microenvironment of symbiotic marine invertebrates is essential for a better understanding of the symbiosis dynamics. Microalgal symbionts (of the family: Symbiodiniaceae) influence diel fluctuations of in host O 2 and pH conditions through their metabolic activities (i.e., photosynthesis and respiration). These variations may play an important role in driving oxygen budgets and energy demands of the holobiont and its responses to climate change. In situ measurements using microsensors were used to resolve the O 2 and pH diel fluctuations in the oral arms of non-calcifying cnidarian model species Cassiopea sp. (the “upside-down jellyfish”), which has an obligatory association with Symbiodiniaceae. Before sunrise, the internal O 2 and pH levels were substantially lower than those in ambient seawater conditions (minimum average levels: 61.92 ± 5.06 1SE μmol O 2 L –1 and 7.93 ± 0.02 1SE pH units, respectively), indicating that conditions within Cassiopea’s oral arms were acidified and hypoxic relative to the surrounding seawater. Measurements performed during the afternoon revealed hyperoxia (maximum average levels: 546.22 ± 16.45 1SE μmol O 2 L –1 ) and internal pH similar to ambient levels (8.61 ± 0.02 1SE pH units). The calculated gross photosynthetic rates of Cassiopea sp. were 0.04 ± 0.013 1SE nmol cm –2 s –1 in individuals collected at night and 0.08 ± 0.02 1SE nmol cm –2 s –1 in individuals collected during the afternoon.

Temperature Significantly Regulates Gene Expressions of Vertebrae Chondrocytes and Osteoblasts in Juvenile Golden Pompano (Trachinotus ovatus) - Mingyang Han; Zhengyi Fu; Rui Yang; Jian G. Qin; Zhenhua Ma (Frontiers in Marine Science, 2021)
To elucidate the possible molecular reaction of vertebral fusion in juvenile golden pompano at high temperature, we examined the changes in growth, vertebral fusion incidence, histological differences and transcription levels of genes related to bone development in juvenile golden pompano at 27 and 33°C for 30 days, respectively. The growth rate of juvenile fish was faster when the water temperature was 33°C, but the incidence of vertebral fusion was higher. Prolonged high water temperature reduced the osteogenic layer in the growth zone of the vertebral endplate and the elastic externa. The endplate growth areas of the fused vertebrae were transformed into cartilage tissue, which was then remodeled into bone. The intervertebral notochord tissue was transformed into bone and the intervertebral space disappeared. In normal phenotypes of vertebrae, short-term high temperature could promote the expression of genes related to cartilage differentiation and maturation, as well as genes related to osteoblastic differentiation. With the increase of culture time, the expression of genes related to cartilage and osteogenesis development was inhibited. In fused vertebrae, cartilage proliferation was enhanced, osteogenic differentiation was inhibited, and matrix mineralization may be enhanced. Genes associated with the development of chondrocytes and osteoblasts in the vertebrae of juvenile Trachinotus ovatus were significantly regulated by temperature and time. The results may contribute to further understanding of the occurrence of vertebral fusion at high temperature.

Genome-wide Identification and Expression Pattern Analysis of the HD-Zip Transcription Factor Family in Pineapple (Ananas Comosus) - Qiao Zhou; Liping Liu; Han Cheng; Zeyun Li; MyatHnin Wai; Tiantian Luo; Xingyue Jin; Heming Zhao; S. V. G. N. Priyadarshani; Yuan Qin (Tropical Plant Biology, 2021)

Diabetes Mellitus/Poststroke Hyperglycemia: a Detrimental Factor for tPA Thrombolytic Stroke Therapy - Yinghua Jiang; Ning Liu; Jinrui Han; Yadan Li; Pierce Spencer; Samuel J. Vodovoz; Ming-Ming Ning; Gregory Bix; Prasad V. G. Katakam; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2021)

ValSten: a new wild species derived allotetraploid for increasing genetic diversity of the peanut crop (Arachis hypogaea L.) - Dongying Gao; Ana C. G. Araujo; Eliza F. M. B. Nascimento; M. Carolina Chavarro; Han Xia; Scott A. Jackson; David J. Bertioli; Soraya C. M. Leal-Bertioli (Genetic Resources and Crop Evolution, 2021)
Introgression of desirable traits from wild relatives plays an important role in crop improvement, as wild species have important characters such as high resistance to pests and pathogens. However, use of wild peanut relatives is challenging because almost all wild species are diploid and sexually incompatible with cultivated peanut, which is tetraploid (AABB genome type; 2 n = 4x = 40). To overcome the ploidy barrier, we used 2 wild species to make a tetraploid with the same allotetraploid genome composition as cultivated peanut. Crosses were made between 2 diploid wild species, Arachis valida Krapov. and W.C. Greg. (BB genome; 2 n = 2x = 20) and Arachis stenosperma Krapov. and W.C. Greg. (AA genome; 2 n = 2x = 20). Cuttings from the diploid F 1 AB hybrid were treated with colchicine to induce chromosome doubling thus generating an induced allotetraploid. Chromosome counts confirmed polyploidy (AABB genome; 2 n = 4x = 40). We named the new allotetraploid ValSten. Plants had well-developed fertile pollen, produced abundant seed and were sexually compatible with cultivated peanut. ValSten exhibits the same high resistance to early and late leaf spot and rust as its diploid parents. Notably, we observed morphological variations, including flower width and branch angles in the earliest generation (S 0 ) of allotetraploids. A SNP array was used to genotype 47 S 0 allotetraploids. The great majority of markers showed the additive allelic state from both parents (AABB). However, some loci were AAAA or BBBB, indicating homeologous recombination. ValSten provides a new, vigorous, highly fertile, disease resistant germplasm for peanut research and improvement.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Cycling in degradation of organic polymers and uptake of nutrients by a litter‐degrading fungus - Aurin M. Vos; Robert‐Jan Bleichrodt; Koen C. Herman; Robin A. Ohm; Karin Scholtmeijer; Heike Schmitt; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2021)
Summary Wood and litter degrading fungi are the main decomposers of lignocellulose and thus play a key role in carbon cycling in nature. Here, we provide evidence for a novel lignocellulose degradation strategy employed by the litter degrading fungus Agaricus bisporus (known as the white button mushroom). Fusion of hyphae allows this fungus to synchronize the activity of its mycelium over large distances (50 cm). The synchronized activity has a 13‐h interval that increases to 20 h before becoming irregular and it is associated with a 3.5‐fold increase in respiration, while compost temperature increases up to 2°C. Transcriptomic analysis of this burst‐like phenomenon supports a cyclic degradation of lignin, deconstruction of (hemi‐) cellulose and microbial cell wall polymers, and uptake of degradation products during vegetative growth of A. bisporus . Cycling in expression of the ligninolytic system, of enzymes involved in saccharification, and of proteins involved in nutrient uptake is proposed to provide an efficient way for degradation of substrates such as litter.

Anthropogenic Contaminants and Histopathological Findings in Stranded Cetaceans in the Southeastern United States, 2012–2018 - Annie Page-Karjian; Catherine F. Lo; Branson Ritchie; Craig A. Harms; David S. Rotstein; Sushan Han; Sayed M. Hassan; Andreas F. Lehner; John P. Buchweitz; Victoria G. Thayer; Jill M. Sullivan; Emily F. Christiansen; et al. (Frontiers in Marine Science, 2020)

MtDNA-Based Phylogeography of the Red Alga Agarophyton vermiculophyllum (Gigartinales, Rhodophyta) in the Native Northwest Pacific - Kai-Le Zhong; Xiao-Han Song; Han-Gil Choi; Shimada Satoshi; Florian Weinberger; Stefano G. A. Draisma; De-Lin Duan; Zi-Min Hu (Frontiers in Marine Science, 2020)

Targeting Two Antigens Associated with B-ALL with CD19-CD123 Compound Car T Cell Therapy - Lulu E. Yan; Hongyu Zhang; Masayuki Wada; Liu Fang; Jia Feng; Wenli Zhang; Qi Chen; Yuanzhen Cao; Kevin G. Pinz; Kevin H. Chen; Jessica C. Petrov; Xi Chen; et al. (Stem Cell Reviews and Reports, 2020)

Acclimation of leaf respiration consistent with optimal photosynthetic capacity - Han Wang; Owen K. Atkin; Trevor F. Keenan; Nicholas G. Smith; Ian J. Wright; Keith J. Bloomfield; Jens Kattge; Peter B. Reich; I. Colin Prentice (Global Change Biology, 2020)
Plant respiration is an important contributor to the proposed positive global carbon‐cycle feedback to climate change. However, as a major component, leaf mitochondrial (‘dark’) respiration ( R d ) differs among species adapted to contrasting environments and is known to acclimate to sustained changes in temperature. No accepted theory explains these phenomena or predicts its magnitude. Here we propose that the acclimation of R d follows an optimal behaviour related to the need to maintain long‐term average photosynthetic capacity ( V cmax ) so that available environmental resources can be most efficiently used for photosynthesis. To test this hypothesis, we extend photosynthetic co‐ordination theory to predict the acclimation of R d to growth temperature via a link to V cmax , and compare predictions to a global set of measurements from 112 sites spanning all terrestrial biomes. This extended co‐ordination theory predicts that field‐measured R d and V cmax accessed at growth temperature ( R d,tg and V cmax,tg ) should increase by 3.7% and 5.5% per degree increase in growth temperature. These acclimated responses to growth temperature are less steep than the corresponding instantaneous responses, which increase 8.1% and 9.9% per degree of measurement temperature for R d and V cmax respectively. Data‐fitted responses proof indistinguishable from the values predicted by our theory, and smaller than the instantaneous responses. Theory and data are also shown to agree that the basal rates of both R d and V cmax assessed at 25°C ( R d,25 and V cmax,25 ) decline by ~4.4% per degree increase in growth temperature. These results provide a parsimonious general theory for R d acclimation to temperature that is simpler—and potentially more reliable—than the plant functional type‐based leaf respiration schemes currently employed in most ecosystem and land‐surface models.

Reciprocal comparison of geodetically sensed and modeled vertical hydrological loading products - Vagner G. Ferreira; Zhiqiang Liu; Henry C. Montecino; Peng Yuan; Caleb I. Kelly; Abubakar S. Mohammed; Lu Y. Han (Acta Geodaetica et Geophysica, 2020)

Stem Cell Mechanosensation on Gelatin Methacryloyl (GelMA) Stiffness Gradient Hydrogels - Claire Kim; Jennifer L. Young; Andrew W. Holle; Kwanghee Jeong; Luke G. Major; Ji Hoon Jeong; Zachary M. Aman; Dong-Wook Han; Yongsung Hwang; Joachim P. Spatz; Yu Suk Choi (Annals of Biomedical Engineering, 2020)

Nonlinear responses of soil nematode community composition to increasing aridity - Dan Xiong; CunZheng Wei; E. R. Jasper Wubs; G. F. Veen; Wenju Liang; Xiaobo Wang; Qi Li; Wim H. Van der Putten; Xingguo Han (Global Ecology and Biogeography, 2020)
Aim Increasing aridity under global change is predicted to have a profound impact on the structure and functioning of terrestrial ecosystems, yet we have a poor understanding of how belowground communities respond. In order to understand the longer term responses of different trophic levels in the soil food web to increasing aridity, we investigated the abundance, richness and community similarity of the soil nematode community along a 3,200 km aridity gradient. Location A transect across semi‐arid and arid grasslands in Northern China, where the aridity ranges from .43 to .97. Time period July and August 2012. Major taxa studied Soil‐borne Nematoda. Methods We used generalized additive (mixed) models to analyse the abundance, richness and community similarity patterns of soil nematodes. We used structural equation modelling (SEM) to disentangle the direct and indirect environmental drivers (aridity, soil and plant variables) of the nematode community. Results The abundance, richness and similarity of nematode communities declined nonlinearly with increasing aridity. The most pronounced decline in nematode richness and community similarity occurred in arid conditions (aridity > .80). However, the shape of the response to aridity differed among nematode feeding groups. In arid conditions, the abundance and richness of bacterial feeders were less sensitive to changes in aridity than for fungal feeders. The SEM analysis revealed that nematode community responses to aridity were not mediated via changes in plant and soil variables, but instead were affected directly by aridity. Main conclusions Our results showed that in mesic grasslands, increasing aridity primarily caused a decline in nematode abundance, whereas increasing aridity in xeric grasslands led to a loss of nematode diversity. The nonlinear responses of nematodes to aridity could also result in nonlinear shifts in ecosystem functioning, because soil nematodes operate at various trophic levels in the soil food web, thereby influencing the performance of plants, soil biodiversity and biogeochemical cycling.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Corrigendum: Night-Time Temperature Reprieves Enhance the Thermal Tolerance of a Symbiotic Cnidarian - Shannon G. Klein; Kylie A. Pitt; Cathy H. Lucas; Shiou-Han Hung; Sebastian Schmidt-Roach; Manuel Aranda; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Relevance of number and physiological status of conspecifics in preventing stress-induced decreases in newly proliferated cells and neuroblasts - Li-Han Sun; Wen-Yu Tzeng; Yi-Han Liao; Wen-Ting Deng; Chianfang G. Cherng; Lung Yu (Psychopharmacology, 2019)

Species diversity and distribution of the genus Colpomenia (Scytosiphonaceae, Phaeophyceae) along the coast of China - Xiao-Han Song; Zi-Min Hu; Zhong-Min Sun; Stefano G. A. Draisma; Pablo Fresia; De-Lin Duan (Algae, 2019)

Night-Time Temperature Reprieves Enhance the Thermal Tolerance of a Symbiotic Cnidarian - Shannon G. Klein; Kylie A. Pitt; Cathy H. Lucas; Shiou-Han Hung; Sebastian Schmidt-Roach; Manuel Aranda; Carlos M. Duarte (Frontiers in Marine Science, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Tremor in the Degenerative Cerebellum: Towards the Understanding of Brain Circuitry for Tremor - Ruo-Yah Lai; Darya Tomishon; Karla P. Figueroa; Stefan M. Pulst; Susan Perlman; George Wilmot; Christopher M. Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G. Shakkottai; Sarah H. Ying; Theresa Zesiewicz; et al. (The Cerebellum, 2019)

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Relevance of the incubation period in cytotoxicity testing with primary human hepatocytes - Xiaolong Gu; Wiebke Albrecht; Karolina Edlund; Franziska Kappenberg; Jörg Rahnenführer; Marcel Leist; Wolfgang Moritz; Patricio Godoy; Cristina Cadenas; Rosemarie Marchan; Tim Brecklinghaus; Laia Tolosa Pardo; et al. (Archives of Toxicology, 2018)

Amyloid-β Increases Tau by Mediating Sirtuin 3 in Alzheimer’s Disease - Junxiang Yin; Pengcheng Han; Melissa Song; Megan Nielsen; Thomas G. Beach; Geidy E. Serrano; Winnie S. Liang; Richard J. Caselli; Jiong Shi (Molecular Neurobiology, 2018)

Confounding influence of tamoxifen in mouse models of Cre recombinase-induced gene activity or modulation - Seddik Hammad; Amnah Othman; Christoph Meyer; Ahmad Telfah; Joerg Lambert; Bedair Dewidar; Julia Werle; Zeribe Chike Nwosu; Abdo Mahli; Christof Dormann; Yan Gao; Kerry Gould; et al. (Archives of Toxicology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Heterotopic Purkinje Cells: a Comparative Postmortem Study of Essential Tremor and Spinocerebellar Ataxias 1, 2, 3, and 6 - Elan D. Louis; Sheng-Han Kuo; William J. Tate; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2018)

Cerebellar Pathology in Familial vs. Sporadic Essential Tremor - Elan D. Louis; Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2017)

The Initial Symptom and Motor Progression in Spinocerebellar Ataxias - Lan Luo; Jie Wang; Raymond Y Lo; Karla P Figueroa; Stefan M Pulst; Pei-Hsin Kuo; Susan Perlman; George Wilmot; Christopher M Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G Shakkottai; et al. (The Cerebellum, 2017)

Cerebellar Pathology in Early Onset and Late Onset Essential Tremor - Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Elan D. Louis; Phyllis L. Faust (The Cerebellum, 2017)

Ectomycorrhizal fungal response to warming is linked to poor host performance at the boreal‐temperate ecotone - Christopher W. Fernandez; Nhu H. Nguyen; Artur Stefanski; Ying Han; Sarah E. Hobbie; Rebecca A. Montgomery; Peter B. Reich; Peter G. Kennedy (Global Change Biology, 2017)
Rising temperatures associated with climate change have been shown to negatively affect the photosynthetic rates of boreal forest tree saplings at their southern range limits. To quantify the responses of ectomycorrhizal ( EM ) fungal communities associated with poorly performing hosts, we sampled the roots of Betula papyrifera and Abies balsamea saplings growing in the B4Warmed (Boreal Forest Warming at an Ecotone in Danger) experiment. EM fungi on the root systems of both hosts were compared from ambient and +3.4 °C air and soil warmed plots at two sites in northern Minnesota. EM fungal communities were assessed with high‐throughput sequencing along with measures of plant photosynthesis, soil temperature, moisture, and nitrogen. Warming selectively altered EM fungal community composition at both the phylum and genus levels, but had no significant effect on EM fungal operational taxonomic unit ( OTU ) diversity. Notably, warming strongly favored EM Ascomycetes and EM fungi with short‐contact hyphal exploration types. Declining host photosynthetic rates were also significantly inversely correlated with EM Ascomycete and EM short‐contact exploration type abundance, which may reflect a shift to less carbon demanding fungi due to lower photosynthetic capacity. Given the variation in EM host responses to warming, both within and between ecosystems, better understanding the link between host performance and EM fungal community structure will to clarify how climate change effects cascade belowground.

Species-rich grassland can persist under nitrogen-rich but phosphorus-limited conditions - Han F. van Dobben; G. W. Wieger Wamelink; Pieter A. Slim; Jan Kamiński; Hubert Piórkowski (Plant and Soil, 2017)

CRIM1 is necessary for coronary vascular endothelial cell development and homeostasis - Swati Iyer; Yash Chhabra; Tracey J. Harvey; Richard Wang; Han Sheng Chiu; A. G. Smith; Walter G. Thomas; David J. Pennisi; Michael Piper (Journal of Molecular Histology, 2017)

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

Detection of a New Hainan Gibbon (Nomascus hainanus) Group Using Acoustic Call Playback - Jessica V. Bryant; Aurélien Brulé; Michelle H. G. Wong; Xiaojiang Hong; Zhaoli Zhou; Wentao Han; Timothy E. Jeffree; Samuel T. Turvey (International Journal of Primatology, 2016)

The effects of petroleum-contaminated soil on photosynthesis of Amorpha fruticosa seedlings - G. Han; B. X. Cui; X. X. Zhang; K. R. Li (International Journal of Environmental Science and Technology, 2016)

Outbreak of hirame rhabdovirus infection in cultured spotted sea bass Lateolabrax maculatus on the western coast of Korea - H‐G Seo; J W Do; S H Jung; H‐J Han (Journal of Fish Diseases, 2016)
In this study, we determined the cause of a disease outbreak in spotted sea bass, Lateolabrax maculatus reared in culture cages on the western coast of Korea in 2013. The major signs in the diseased fish exhibited were haemorrhaging on the membranes of the abdomen, gastrointestinal organs and opercular gills, as well as an enlarged spleen. No external morphological signs of infection were visible, except for a darkening in colour. No parasites or pathological bacteria were isolated from the diseased fish; however, epithelioma papulosum cyprini ( EPC ) cells inoculated with tissue homogenates from the diseased fish showed cytopathic effects ( CPE s). Virus particles in the EPC cells were bullet‐shaped, 185–225 nm long and 70–80 nm wide, characteristic of Rhabdoviridae. Polymerase chain reaction analyses of homogenized tissues from the diseased fish and supernatants of cell cultures with CPE s indicated specific, 553‐bp‐long fragments corresponding to the matrix protein gene of the hirame rhabdovirus ( HIRRV ). Phylogenetically, the HIRRV phosphoprotein gene of spotted sea bass was more closely related to phosphoproteins from Chinese and Polish HIRRV strains than from other Korean strains. To our knowledge, this is the first report of HIRRV infection in cultured spotted sea bass.

Vegetation, fire, and climate history during the last 18 500 cal a BP in south‐western Yunnan Province, China - Xiayun Xiao; J. I. Shen; Simon G. Haberle; Yong Han; Bin Xue; Enlou Zhang; Sumin Wang; Guobang Tong (Journal of Quaternary Science, 2015)
High‐resolution pollen and charcoal records from Qinghai Lake in south‐western China are presented. The records reveal variations in vegetation, fire and climate history since 18 500 cal a BP. The results show that seven significant vegetation changes are recorded, which are responses to climate changes and/or fire events. Frequent and intensive fires occurred during the periods 17 900–15 000, 13 000–11 500 and 4280–980 cal a BP, corresponding to relatively dry climatic conditions. Combined with the climatic record from Tiancai Lake, the regional climatic changes since 18 500 cal a BP in western Yunnan Province are reconstructed. Namely, the Heinrich Event 1, the Bølling–Allerød warm period and the Younger Dryas event during the last deglaciation are ubiquitous in western Yunnan Province. The start of the Holocene is recorded at 11 500 cal a BP. The Holocene climatic optimum occurred between 8450 and 4280 cal a BP. After 4280 cal a BP, the climate deteriorated, accompanied by evidence for human impact. Based on this study, we consider that vegetation and climatic changes since 18 500 cal a BP in south‐western Yunnan Province are primarily driven by September and average summer solar insolation, with some associated influence from regional sea‐surface temperature and sea‐level rise.

Evaluation of the protective effect of Pterocarpus marsupium on acetic acid-induced ulcerative colitis in rats - Merin Maria Mathew; Nguyen Vinh Han; A. Murugesan; E. Arun Raj; K. G. Prasanth (Inflammopharmacology, 2015)

Genetic polymorphism of APOB is associated with diabetes mellitus in sickle cell disease - Xu Zhang; Wei Zhang; Santosh L. Saraf; Mehdi Nouraie; Jin Han; Michel Gowhari; Johara Hassan; Galina Miasnikova; Adelina Sergueeva; Sergei Nekhai; Rick Kittles; Roberto F. Machado; et al. (Human Genetics, 2015)

The Domain II S4-S5 Linker in Nav1.9: A Missense Mutation Enhances Activation, Impairs Fast Inactivation, and Produces Human Painful Neuropathy - Chongyang Han; Yang Yang; Bianca T. A. de Greef; Janneke G. J. Hoeijmakers; Monique M. Gerrits; Camiel Verhamme; Jian Qu; Giuseppe Lauria; Ingemar S. J. Merkies; Catharina G. Faber; Sulayman D. Dib-Hajj; Stephen G. Waxman (NeuroMolecular Medicine, 2015)

Effect of stem radial growth on seasonal and spatial variations in stem CO2 efflux of Chamaecyparis obtusa - Masatake G. Araki; Takuya Kajimoto; Qingmin Han; Tatsuro Kawasaki; Hajime Utsugi; Koichiro Gyokusen; Yukihiro Chiba (Trees, 2015)

Influence of Constant Temperature on Development and Reproduction of Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a Parasitoid of the Spiraling Whitefly Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - J Y Chen; L M Niu; L Li; D Y Han; Y G Fu (Neotropical Entomology, 2015)

Hymenoscyphus fraxineus and two new Hymenoscyphus species identified in Korea - A. Gross; J. G. Han (Mycological Progress, 2015)

Host-Choice Behavior of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) Under Laboratory Conditions - Chuan-Qing Ruan; David G. Hall; Bo Liu; Yong-Ping Duan; Tao Li; Han-Qing Hu; Guo-Cheng Fan (Journal of Insect Behavior, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Decreased consumption of rewarding sucrose solutions after injection of melanocortins into the ventral tegmental area of rats - Haw-Han Yen; Aaron G. Roseberry (Psychopharmacology, 2015)

VEGF neutralization can prevent and normalize arteriovenous malformations in an animal model for hereditary hemorrhagic telangiectasia 2 - Chul Han; Se-woon Choe; Yong Hwan Kim; Abhinav P. Acharya; Benjamin G. Keselowsky; Brian S. Sorg; Young-Jae Lee; S. Paul Oh (Angiogenesis, 2014)

Limited diagnostic value of microsatellite instability associated pathology features in colorectal cancer - Paul G. van Putten; Margot G. F. van Lier; Mariska Hage; Katharina Biermann; Reinier H. van Rijssel; Pieter J. Westenend; Hans Morreau; Ewout W. Steyerberg; Winand N. M. Dinjens; Ernst J. Kuipers; Monique E. van Leerdam; J. Han van Krieken (Familial Cancer, 2014)

Torpedo Formation and Purkinje Cell Loss: Modeling their Relationship in Cerebellar Disease - Elan D. Louis; Sheng-Han Kuo; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2014)

Effects of Transduction of the bcl-2 Gene and of Nerve Growth Factor on Apoptosis of Cultured PC12 Cells - G. Han; W. Wei; X. Zhang; Zh. Lai; Ch. Chen (Neurophysiology, 2014)

Erratum to: Rapid Determination of Mercury in Contaminated Soil and Plant Samples Using Portable Mercury Direct Analyzer Without Sample Preparation, a Comparative Study - John G. Kelly; Fengxiang X. Han; Yi Su; Yunjun Xia; Valerie Philips; Zhiqi Shi; David L. Monts; Sergio T. Pichardo; Kang Xia (Water, Air, & Soil Pollution, 2014)

Adsorption of anionic dye on magnesium hydroxide-coated pyrolytic bio-char and reuse by microwave irradiation - X. N. Zhang; G. Y. Mao; Y. B. Jiao; Y. Shang; R. P. Han (International Journal of Environmental Science and Technology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Identification of the Major Sex Pheromone Component of the Scale Insect, Aulacaspis murrayae Takahashi - Hsiao-Yung Ho; Bowroju Suresh Kuarm; Chi-Hung Ke; Yi-Kai Ma; Han-Jung Lee; Chao-Chih Cheng; Kelvin Kwen Liu; Jocelyn G. Millar (Journal of Chemical Ecology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Molecular mapping of a stripe rust resistance gene in wheat cultivar Wuhan 2 - X. L. Zhou; D. J. Han; H. L. Gou; Q. L. Wang; Q. D. Zeng; F. P. Yuan; G. M. Zhan; L. L. Huang; Z. S. Kang (Euphytica, 2014)
Stripe rust (or yellow rust), caused by Puccinia striiformis f. sp. tritici , is one of the most destructive diseases of wheat worldwide. Growing resistant cultivars is the best approach to control the disease. To identify and map genes for stripe rust resistance in wheat cultivar ‘Wuhan 2', an F 2 population was developed from a cross between the cultivar and susceptible cultivar Mingxian 169. The parents, 179 F 2 plants and their derived F 2:3 lines were evaluated for responses to Chinese races CYR30 and CYR31 of the pathogen in a greenhouse. A recessive gene for resistance was identified. DNA bulked segregant analysis was applied and resistance gene analog polymorphism (RGAP) and simple sequence repeat (SSR) techniques were used to identify molecular markers linked to the resistance gene. A genetic map consisting of five RGAP and six SSR markers was constructed. The recessive gene, designated Yrwh2 , was located on the short arm of chromosome 3B and flanked by SSR markers Xwmc540 and Xgwm566 at 5.9 and 10.0 cM, respectively. The chromosomal location of the resistance gene and its close marker suggest that the locus is different from previously reported stripe rust resistance genes Yr30 , QYr.ucw - 3BS , Yrns - B1 , YrRub and QYrex.wgp - 3BL previously mapped to chromosome 3B. Yrwh2 and its closely linked markers are potentially useful for developing stripe rust resistance wheat cultivars if used in combination with other genes.

The value of multiple earthquake missions: the EEFIT L’Aquila Earthquake experience - T. Rossetto; D. D’Ayala; F. Gori; R. Persio; J. Han; V. Novelli; S. M. Wilkinson; D. Alexander; M. Hill; S. Stephens; S. Kontoe; G. Elia; et al. (Bulletin of Earthquake Engineering, 2014)

Applications of capillary electrophoresis for rapidly separating and characterizing water-soluble proteins of wheat grains - C. Han; Z. Yu; S. Feng; D. Lv; X. Yan; G. Chen; X. Li; W. Ma; Y. Yan (Cereal Research Communications, 2013)

Challenge of weed risk assessment (WRA) for ecological restoration in China: The case of Rhus typhina L. and the new officially released weed risk assessment system - G. M. Wang; J. C. Yang; C. D. Jiang; G. M. Jiang; J. B. Yu; H. B. Shao; G. X. Han; Y. J. Gao (Plant Biosystems, 2013)

Genetic variations in the myostatin gene (MSTN) in New Zealand sheep breeds - J. Han; R. H. Forrest; J. G. H. Hickford (Molecular Biology Reports, 2013)

β-Ionone arrests cell cycle of gastric carcinoma cancer cells by a MAPK pathway - Hong-Wei Dong; Shuang Zhang; Wen-Guang Sun; Qian Liu; Juan C. Ibla; Sulpicio G. Soriano; Xiao-Hui Han; Lian-Xin Liu; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

More breast cancer patients prefer BRCA-mutation testing without prior face-to-face genetic counseling - Aisha S. Sie; Wendy A. G. van Zelst-Stams; Liesbeth Spruijt; Arjen R. Mensenkamp; Marjolijn J. L. Ligtenberg; Han G. Brunner; Judith B. Prins; Nicoline Hoogerbrugge (Familial Cancer, 2013)

Mapping quantitative trait loci for tissue culture response in VCS3M-DH population of Brassica rapa - Mi-Suk Seo; Mina Jin; Soo-Seong Lee; Soo-Jin Kwon; Jeong-Hwan Mun; Beom-Seok Park; Richard G. F. Visser; Guusje Bonnema; Seong-Han Sohn (Plant Cell Reports, 2013)

Heterogeneity in the mycelium: implications for the use of fungi as cell factories - Han A. B. Wösten; G. Jerre van Veluw; C. de Bekker; Pauline Krijgsheld (Biotechnology Letters, 2013)

Evaluation of organic contamination in urban groundwater surrounding a municipal landfill, Zhoukou, China - D. M. Han; X. X. Tong; M. G. Jin; Emily Hepburn; C. S. Tong; X. F. Song (Environmental Monitoring and Assessment, 2013)

Fruit production in three masting tree species does not rely on stored carbon reserves - Günter Hoch; Rolf T. W. Siegwolf; Sonja G. Keel; Christian Körner; Qingmin Han (Oecologia, 2013)

Comparison of wavelet estimation methods - Bo Y. Yi; Gwang H. Lee; Han-Joon Kim; Hyeong-Tae Jou; Dong G. Yoo; Byong J. Ryu; Keumsuk Lee (Geosciences Journal, 2013)

Absence of induced resistance in Agaricus bisporus against Lecanicillium fungicola - Roeland L. Berendsen; Niek Schrier; Stefanie I. C. Kalkhove; Luis G. Lugones; Johan J. P. Baars; Carolien Zijlstra; Marjanne de Weerdt; Han A. B. Wösten; Peter A. H. M. Bakker (Antonie van Leeuwenhoek, 2013)

The blue light receptor complex WC ‐1/2 of S chizophyllum commune is involved in mushroom formation and protection against phototoxicity - Robin A. Ohm; David Aerts; Han A. B. Wösten; Luis G. Lugones (Environmental Microbiology, 2013)
Summary Blue light is necessary for initiation of mushroom formation in S chizophyllum commune . The genome of this basidiomycete contains homologues of the blue light receptor genes wc‐1 and wc‐2 of N eurospora crassa . Here, it is shown that inactivation of either or both of these genes in S . commune results in a blind phenotype. Mushroom formation was abolished in dikaryons and they formed symmetrical instead of asymmetrical colonies. Development was restored in a temperature dependent way in a Δ wc‐2 Δ wc‐2 strain by introducing a construct encompassing the wc‐2 gene under control of the promoter of the heat shock gene hsp3 . A genome‐wide expression analysis showed that the transcription factor genes c2h2 and hom1 as well as many hydrophobin genes are downregulated in light‐grown colonies of the Δ wc‐2 Δ wc‐2 mutant when compared with the wild‐type dikaryon. Inactivation of wc‐1 and/or wc‐2 also resulted in sensitivity of the mycelium to intense light. Monokaryotic mutant strains only survived exposure to 6500 lux of light by growing into the agar. Expression analysis indicates that the photosensitivity of the Δ wc‐1 and Δ wc‐2 strains is due to lower levels of photolyase and ferrochelatase.

Testing the metabolic theory of ecology - Charles A. Price; Joshua S Weitz; Van M. Savage; James Stegen; Andrew Clarke; David A. Coomes; Peter S. Dodds; Rampal S. Etienne; Andrew J. Kerkhoff; Katherine McCulloh; Karl J. Niklas; Han Olff; et al. (Ecology Letters, 2012)
The metabolic theory of ecology (MTE) predicts the effects of body size and temperature on metabolism through considerations of vascular distribution networks and biochemical kinetics. MTE has also been extended to characterise processes from cellular to global levels. MTE has generated both enthusiasm and controversy across a broad range of research areas. However, most efforts that claim to validate or invalidate MTE have focused on testing predictions. We argue that critical evaluation of MTE also requires strong tests of both its theoretical foundations and simplifying assumptions. To this end, we synthesise available information and find that MTE's original derivations require additional assumptions to obtain the full scope of attendant predictions. Moreover, although some of MTE's simplifying assumptions are well supported by data, others are inconsistent with empirical tests and even more remain untested. Further, although many predictions are empirically supported on average, work remains to explain the often large variability in data. We suggest that greater effort be focused on evaluating MTE's underlying theory and simplifying assumptions to help delineate the scope of MTE, generate new theory and shed light on fundamental aspects of biological form and function.

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Neuroglial Expression of the MHCI Pathway and PirB Receptor Is Upregulated in the Hippocampus with Advanced Aging - Heather D. VanGuilder Starkey; Colleen A. Van Kirk; Georgina V. Bixler; Caesar G. Imperio; Vijay P. Kale; Jacob M. Serfass; Julie A. Farley; Han Yan; Junie P. Warrington; Song Han; Matthew Mitschelen; William E. Sonntag; et al. (Journal of Molecular Neuroscience, 2012)

Prolonged exclusive breastfeeding, autumn birth and increased gestational age are associated with lower risk of fever in children with hand, foot, and mouth disease - Q. Zhu; Y. Li; N. Li; Q. Han; Z. Liu; Z. Li; J. Qiu; G. Zhang; F. Li; N. Tian (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Desulfohalophilus alkaliarsenatis gen. nov., sp. nov., an extremely halophilic sulfate- and arsenate-respiring bacterium from Searles Lake, California - Jodi Switzer Blum; Thomas R. Kulp; Sukkyun Han; Brian Lanoil; Chad W. Saltikov; John F. Stolz; Laurence G. Miller; Ronald S. Oremland (Extremophiles, 2012)

Insects perceive local sex ratio in the absence of tactile or visual sex-specific cues - Chang S. Han; Chang-Ku Kang; Hong-Sup Shin; Jeong-Hyun Lee; Mi-Rye Bae; Sang-Im Lee; Piotr G. Jablonski (Behavioral Ecology and Sociobiology, 2012)

Rapid Determination of Mercury in Contaminated Soil and Plant Samples Using Portable Mercury Direct Analyzer without Sample Preparation, a Comparative Study - John G. Kelly; Fengxiang X. Han; Yi Su; Yunjun Xia; Valerie Philips; Zhiqi Shi; David L. Monts; Sergio T. Pichardo; Kang Xia (Water, Air, & Soil Pollution, 2012)

Integrating pathway analysis and genetics of gene expression for genome-wide association study of basal cell carcinoma - Mingfeng Zhang; Liming Liang; Nilesh Morar; Anna L. Dixon; G. Mark Lathrop; Jun Ding; Miriam F. Moffatt; William O. C. Cookson; Peter Kraft; Abrar A. Qureshi; Jiali Han (Human Genetics, 2012)

An intronic MYLK variant associated with inflammatory lung disease regulates promoter activity of the smooth muscle myosin light chain kinase isoform - Yoo Jeong Han; Shwu-Fan Ma; Michael S. Wade; Carlos Flores; Joe G. N. Garcia (Journal of Molecular Medicine, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Managing invasions at the cost of native habitat? An experimental test of the impact of fire on the invasion of Chromolaena odorata in a South African savanna - Mariska te Beest; Joris P. G. M. Cromsigt; Johan Ngobese; Han Olff (Biological Invasions, 2012)

Large grazers modify effects of aboveground–belowground interactions on small-scale plant community composition - G. F. Veen; Elzemiek Geuverink; Han Olff (Oecologia, 2012)

Genomic sequence of infectious hypodermal and hematopoietic necrosis virus (IHHNV) KLV-2010-01 originating from the first Korean outbreak in cultured Litopenaeus vannamei - J. H. Kim; H. K. Kim; V. G. Nguyen; B. K. Park; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Effects of Erosion from Mounds of Different Termite Genera on Distinct Functional Grassland Types in an African Savannah - Cleo M. Gosling; Joris P. G. M. Cromsigt; Nokukhanya Mpanza; Han Olff (Ecosystems, 2012)

A High Arctic soil ecosystem resists long‐term environmental manipulations - ERIC G. LAMB; SUKKYUN HAN; BRIAN D. LANOIL; GREG H. R. HENRY; MARTIN E. BRUMMELL; SAMIRAN BANERJEE; STEVEN D. SICILIANO (Global Change Biology, 2011)
We evaluated above‐ and belowground ecosystem changes in a 16 year, combined fertilization and warming experiment in a High Arctic tundra deciduous shrub heath (Alexandra Fiord, Ellesmere Island, NU, Canada). Soil emissions of the three key greenhouse gases (GHGs) (carbon dioxide, methane, and nitrous oxide) were measured in mid‐July 2009 using soil respiration chambers attached to a FTIR system. Soil chemical and biochemical properties including Q 10 values for CO 2 , CH 4 , and N 2 O, Bacteria and Archaea assemblage composition, and the diversity and prevalence of key nitrogen cycling genes including bacterial amoA , crenarchaeal amoA , and nosZ were measured. Warming and fertilization caused strong increases in plant community cover and height but had limited effects on GHG fluxes and no substantial effect on soil chemistry or biochemistry. Similarly, there was a surprising lack of directional shifts in the soil microbial community as a whole or any change at all in microbial functional groups associated with CH 4 consumption or N 2 O cycling in any treatment. Thus, it appears that while warming and increased nutrient availability have strongly affected the plant community over the last 16 years, the belowground ecosystem has not yet responded. This resistance of the soil ecosystem has resulted in limited changes in GHG fluxes in response to the experimental treatments.

Health Risk Assessment of Organochlorine Contaminants in Fish from a Major Lake (Baiyangdian Lake) in North China - G. H. Dai; X. H. Liu; G. Liang; M. Z. Xu; X. Han; L. Shi (Bulletin of Environmental Contamination and Toxicology, 2011)

Increase in Rubisco activity and gene expression due to elevated temperature partially counteracts ultraviolet radiation–induced photoinhibition in the marine diatom Thalassiosira weissflogii - E. Walter Helbling; Anita G. J. Buma; Peter Boelen; Han J. van der Strate; M. Valeria Fiorda Giordanino; Virginia E. Villafañe (Limnology and Oceanography, 2011)
We performed outdoor experiments to evaluate the effect of temperature on photoinhibition properties in the cosmopolitan diatom Thalassiosira weissflogii . Cultures were exposed to solar radiation with or without ultraviolet radiation (UVR, 280–400 nm), UV‐A (320–400 nm), and UV‐B (280–320 nm) at both 20°C and 25°C. Four possible cellular mechanisms involved in UVR stress were simultaneously addressed: carbon incorporation, chlorophyll a fluorescence of photosystem II, xanthophyll cycle activity, and ribulose‐1,5‐biphosphate carboxylase : oxygenase (Rubisco) activity and gene expression. Experiments consisted of daily cycles (i.e., the daylight period) and short‐term incubations (i.e., 1 h centered on local noon). Samples incubated at 25°C had significantly less UVR‐induced inhibition of carbon fixation and effective photochemical quantum yield compared to those incubated at 20°C. At 25°C Rubisco activity and gene expression were significantly higher than at 20°C. The higher Rubisco activity and gene expression were correlated with less dissipation of excess energy, evaluated via non‐photochemical quenching, and the de‐epoxidation state of the xanthophyll pigments, as more photons could be processed. An increase in temperature due to climate change would partially counteract the negative effects of UVR by increasing the response of metabolic pathways, such as those involved in Rubisco. This, in turn, may have important consequences for the ecosystem, as higher production (due to more Rubisco activity) could be expected under a scenario of global warming.

A new total volume model of debris flows with intermittent surges: based on the observations at Jiangjia Valley, southwest China - N. Sh. Chen; Ch. L. Yang; W. Zhou; F. Q. Wei; Z. L. Li; D. Han; G. Sh. Hu (Natural Hazards, 2011)

A Matched Asymptotic Expansion Analysis of Highly Unsteady Porous Media Flows - S. Y. Han; D. Hansen; G. C. Kember (Transport in Porous Media, 2010)

An efficient gene deletion procedure for the mushroom-forming basidiomycete Schizophyllum commune - Robin A. Ohm; Jan F. de Jong; Elsa Berends; Fengfeng Wang; Han A. B. Wösten; Luis G. Lugones (World Journal of Microbiology and Biotechnology, 2010)

Master donor viruses A/Leningrad/134/17/57 (H2N2) and B/USSR/60/69 and derived reassortants used in live attenuated influenza vaccine (LAIV) do not display neurovirulent properties in a mouse model - J. Theo M. Voeten; Irina V. Kiseleva; Harrie L. Glansbeek; Stephanie M. C. Basten; Sandra K. M. Drieszen-van der Cruijsen; Larisa G. Rudenko; Han van den Bosch; Jacco G. M. Heldens (Archives of Virology, 2010)

Determination of Imazaquin and its Metabolite by Liquid Chromatography-Quadrupole-Time of Flight Tandem Mass - H. B. Yao; G. J. Han; G. X. Liu; Y. Xie; C. H. Wang (Bulletin of Environmental Contamination and Toxicology, 2010)

A first genetic linkage map of bluegill sunfish (Lepomis macrochirus) using AFLP markers - Wei-Ji Wang; Han-Ping Wang; Hong Yao; Geoff K. Wallat; Laura G. Tiu; Qing-Yin Wang (Aquaculture International, 2010)

Brown algae (Phaeophyceae) from Russian Far Eastern seas: re-evaluation of Laminaria multiplicata Petrov et Suchovejeva - Tatyana A. Klochkova; Gwang-Hoon Kim; Kyung-Min Lee; Han-Gu Choi; Mihail N. Belij; Nina G. Klochkova (Algae, 2010)

Human Enteric Viruses in Groundwater - S. H. Park; E. J. Kim; T. H. Yun; J. H. Lee; C. K. Kim; Y. H. Seo; S. A. Oh; S. S. Choi; S. J. Cho; M. S. Kim; G. Y. Han; M. Y. Kim; et al. (Food and Environmental Virology, 2010)

Female BRCA mutation carriers with a preference for prophylactic mastectomy are more likely to participate an educational-support group and to proceed with the preferred intervention within 2 years - Karin M. Landsbergen; Judith B. Prins; Yvonne J. L. Kamm; Han G. Brunner; Nicoline Hoogerbrugge (Familial Cancer, 2010)

Role of body size in dominance interactions between male water striders, Aquarius paludum - Chang S. Han; Piotr G. Jablonski (Journal of Ethology, 2010)

Comparison of reproductive development in triploid and diploid female rainbow trout Oncorhynchus mykiss - Y. Han; M. Liu; L. Lan Zhang; B. Simpson; G. Xue Zhang (Journal of Fish Biology, 2010)
The diploid rainbow trout Oncorhynchus mykiss reached sexual maturity 3 years after hatching and its oogenesis underwent four stages, which were oogonia, primary oocyte, secondary oocyte and egg. Reproductive development and hormone changes of 4 to 35 month‐old female O. mykiss were investigated using histological and radioimmunoassay methods in order to provide a theoretical and practical basis for the use of triploid female O. mykiss . The oogonium of the triploid female could develop into the oocytes of the prophase with abortion occurring later; the oogonium was surrounded by stroma cells to form the oogonium cluster and the gonads showed a virilescent tendency when the oogonium clusters were gradually replaced by spermatogenic‐like cytocysts. After 13 months, amounts of gonadotropic hormone (GtH‐I, GtH‐II) and oestradiol (17 β ‐E 2 ) in triploid females were lower than in diploid fish at corresponding time periods, but the amounts of testosterone (T) increased consistently after 21 months and were more than in diploid fish in the corresponding time periods ( P > 0·05). The infertility of triploid females resulted from meiosis failure, which caused developmental abortion of oocytes and oogonium formed cytocysts before the prophase oocytes. The cytocyst formation was due to the lack of the normal interaction of ovum and follicular cells, the development of follicular cells producing steroids were inhibited, the arylate path from T to 17 β ‐E 2 was interrupted, concentration of 17 β ‐E 2 decreased and concentration of T increased in the blood, the content of vitellogenin (Vg) decreased in the liver with a low 17 β ‐E 2 and high T caused to ovaries to show a tendency to be virilescent.

The septal pore cap is an organelle that functions in vegetative growth and mushroom formation of the wood‐rot fungus Schizophyllum commune - Arend F. Van Peer; Fengfeng Wang; Kenneth G. A. Van Driel; Jan F. De Jong; Elly G. Van Donselaar; Wally H. Müller; Teun Boekhout; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2010)
Summary Mushroom‐forming basidiomycetes colonize large areas in nature. Their hyphae are compartmentalized by perforated septa, which are usually covered by a septal pore cap (SPC). Here, we describe, for the first time, the composition and function of SPCs using the model system Schizophyllum commune . The SPC of S. commune was shown to consist of a proteinaceous matrix covered by a lipid membrane. The matrix was demonstrated to define the ultrastructure of the SPC and to consist of two main proteins, Spc14 and Spc33. Gene spc14 encodes a protein of 86 amino acids, which lacks known domain, signal or localization sequences. Gene spc33 encodes a 239 and a 340 amino acid variant. Both forms contain a predicted signal anchor that targets them to the ER. Immuno‐localization showed the presence of Spc33 in the SPC but not in ER. From this and previous reports it is concluded that the SPC is derived from this organelle. Inactivation of spc33 resulted in loss of SPCs and the inability to close septa. The latter may well explain why vegetative growth and mushroom formation were severely reduced in strains in which spc33 was inactivated.

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Vertebrate herbivores influence soil nematodes by modifying plant communities - G. F. (Ciska) Veen; Han Olff; Henk Duyts; Wim H. van der Putten (Ecology, 2010)
Abiotic soil properties, plant community composition, and herbivory all have been reported as important factors influencing the composition of soil communities. However, most studies thus far have considered these factors in isolation, whereas they strongly interact in the field. Here, we study how grazing by vertebrate herbivores influences the soil nematode community composition of a floodplain grassland while we account for effects of grazing on plant community composition and abiotic soil properties. Nematodes are the most ubiquitous invertebrates in the soil. They include a variety of feeding types, ranging from microbial feeders to herbivores and carnivores, and they perform key functions in soil food webs. Our hypothesis was that grazing affects nematode community structure and composition through altering plant community structure and composition. Alternatively, we tested whether the effects of grazing may, directly or indirectly, run via changes in soil abiotic properties. We used a long‐term field experiment containing plots with and without vertebrate grazers (cattle and rabbits). We compared plant and nematode community structure and composition, as well as a number of key soil abiotic properties, and we applied structural equation modeling to investigate four possible pathways by which grazing may change nematode community composition. Aboveground grazing increased plant species richness and reduced both plant and nematode community heterogeneity. There was a positive relationship between plant and nematode diversity indices. Grazing decreased the number of bacterial‐feeding nematodes, indicating that in these grasslands, top‐down control of plant production by grazing leads to bottom‐up control in the basal part of the bacterial channel of the soil food web. According to the structural equation model, grazing had a strong effect on soil abiotic properties and plant community composition, whereas plant community composition was the main determinant of nematode community composition. Other pathways, which assumed that grazing influenced nematode community composition by inducing changes in soil abiotic properties, did not significantly explain variation in nematode community composition. We conclude that grazing‐induced changes in nematode community composition mainly operated via changes in plant community composition. Influences of vertebrate grazers on soil nematodes through modification of abiotic soil properties were of less importance.

Genetic testing for Lynch syndrome in the first year of colorectal cancer: a review of the psychological impact - Karin M. Landsbergen; Judith B. Prins; Han G. Brunner; Floris W. Kraaimaat; Nicoline Hoogerbrugge (Familial Cancer, 2009)

Molecular characterization of hepatitis A virus isolated from acute gastroenteritis patients in the Seoul region of Korea - S.-H. Park; E.-J. Kim; J.-H. Lee; S.-S. Choi; M.-S. Kim; S.-S. Jung; G.-Y. Han; H.-S. Yun; D.-S. Chun; S.-S. Oh; H.-S. Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Physicochemical and Immunological Characterization of N,N,N-Trimethyl Chitosan-Coated Whole Inactivated Influenza Virus Vaccine for Intranasal Administration - Niels Hagenaars; Enrico Mastrobattista; Rolf J. Verheul; Imke Mooren; Harrie L. Glansbeek; Jacco G. M. Heldens; Han van den Bosch; Wim Jiskoot (Pharmaceutical Research, 2009)

Monitoring large herbivore diversity at different scales: comparing direct and indirect methods - Joris P. G. M. Cromsigt; Susan J. van Rensburg; Rampal S. Etienne; Han Olff (Biodiversity and Conservation, 2009)

Efficient, reproducible Agrobacterium-mediated transformation of sorghum using heat treatment of immature embryos - Songul Gurel; Ekrem Gurel; Rajvinder Kaur; Joshua Wong; Ling Meng; Han-Qi Tan; Peggy G. Lemaux (Plant Cell Reports, 2009)

Detection of Autoinducer-2 and Analysis of the Profile of luxS and pfs Transcription in Streptococcus suis Serotype 2 - X. G. Han; C. P. Lu (Current Microbiology, 2009)

Resistance to race 2 and cross-resistance to race 1 of Kabatiella caulivora in Trifolium subterraneum and T. purpureum - Hua Li; P. G. H. Nichols; S. Han; K. J. Foster; K. Sivasithamparam; M. J. Barbetti (Australasian Plant Pathology, 2009)

The complete genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ) - Elizabeth Pierce; Gary Xie; Ravi D. Barabote; Elizabeth Saunders; Cliff S. Han; John C. Detter; Paul Richardson; Thomas S. Brettin; Amaresh Das; Lars G. Ljungdahl; Stephen W. Ragsdale (Environmental Microbiology, 2008)
Summary This paper describes the genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ), which is the model acetogenic bacterium that has been widely used for elucidating the Wood–Ljungdahl pathway of CO and CO 2 fixation. This pathway, which is also known as the reductive acetyl‐CoA pathway, allows acetogenic (often called homoacetogenic) bacteria to convert glucose stoichiometrically into 3 mol of acetate and to grow autotrophically using H 2 and CO as electron donors and CO 2 as an electron acceptor. Methanogenic archaea use this pathway in reverse to grow by converting acetate into methane and CO 2 . Acetogenic bacteria also couple the Wood–Ljungdahl pathway to a variety of other pathways to allow the metabolism of a wide variety of carbon sources and electron donors (sugars, carboxylic acids, alcohols and aromatic compounds) and electron acceptors (CO 2 , nitrate, nitrite, thiosulfate, dimethylsulfoxide and aromatic carboxyl groups). The genome consists of a single circular 2 628 784 bp chromosome encoding 2615 open reading frames (ORFs), which includes 2523 predicted protein‐encoding genes. Of these, 1834 genes (70.13%) have been assigned tentative functions, 665 (25.43%) matched genes of unknown function, and the remaining 24 (0.92%) had no database match. A total of 2384 (91.17%) of the ORFs in the M. thermoacetica genome can be grouped in orthologue clusters. This first genome sequence of an acetogenic bacterium provides important information related to how acetogens engage their extreme metabolic diversity by switching among different carbon substrates and electron donors/acceptors and how they conserve energy by anaerobic respiration. Our genome analysis indicates that the key genetic trait for homoacetogenesis is the core acs gene cluster of the Wood–Ljungdahl pathway.

Effects of brassinolide on the survival, growth and drought resistance of Robinia pseudoacacia seedlings under water-stress - K. R. Li; H. H. Wang; G. Han; Q. J. Wang; J. Fan (New Forests, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Changes in Chlorophyll Fluorescence in Maize Plants with Imposed Rapid Dehydration at Different Leaf Ages - Z. Z. Xu; G. S. Zhou; Y. L. Wang; G. X. Han; Y. J. Li (Journal of Plant Growth Regulation, 2008)

Sea level and geostrophic current features from tandem TOPEX/Poseidon‐Jason data in the Newfoundland offshore - G. Han; J. Li (International Journal of Remote Sensing, 2008)

Genotypic differences in leaf biochemical, physiological and growth responses to ozone in 20 winter wheat cultivars released over the past 60 years - D. K. BISWAS; H. XU; Y. G. LI; J. Z. SUN; X. Z. WANG; X. G. HAN; G. M. JIANG (Global Change Biology, 2008)
Ozone (O 3 ) concentrations in periurban areas in East Asia are sufficiently high to decrease crop yield. However, little is known about the genotypic differences in O 3 sensitivity in winter wheat in relation to year of cultivar release. This paper reports genotypic variations in O 3 sensitivity in 20 winter wheat cultivars released over the past 60 years in China highlighting O 3 ‐induced mechanisms. Wheat plants were exposed to elevated O 3 (82 ppb O 3 , 7 h day −1 ) or charcoal‐filtered air ( 3 ) for 21 days in open top chambers. Responses to O 3 were assessed by the levels of antioxidative activities, protein alteration, membrane lipid peroxidation, gas exchange, leaf chlorophyll, dark respiration and growth. We found that O 3 significantly reduced foliar ascorbate (−14%) and soluble protein (−22%), but increased peroxidase activity (+46%) and malondialdehyde (+38%). Elevated O 3 depressed light saturated net photosynthetic rate (−24%), stomatal conductance (−8%) and total chlorophyll (−11%), while stimulated dark respiration (+28%) and intercellular CO 2 concentration (+39%). O 3 also reduced overall plant growth, but to a greater extent in root (−32%) than in shoot (−17%) biomass. There was significant genotypic variation in potential sensitivity to O 3 that did not correlate to observed O 3 tolerance. Sensitivity to O 3 in cultivars of winter wheat progressed with year of release and correlated with stomatal conductance and dark respiration in O 3 ‐exposed plants. O 3 ‐induced loss in photosynthetic rate was attributed primarily to impaired activity of mesophyll cells and loss of integrity of cellular membrane as evidenced by increased intercellular CO 2 concentration and lipid peroxidation. Our findings demonstrated that higher sensitivity to O 3 in the more recently released cultivars was induced by higher stomatal conductance, larger reduction in antioxidative capacity and lower levels of dark respiration leading to higher oxidative damage to proteins and integrity of cellular membranes.

Sex Differences in the Steepness of Dominance Hierarchies in Captive Bonobo Groups - Jeroen M. G. Stevens; Hilde Vervaecke; Han de Vries; Linda van Elsacker (International Journal of Primatology, 2007)

Characteristics of reactive nitrogen compounds and other relevant trace gases in the atmosphere at urban and rural areas of Korea during May–June, 2004 - Z.-H. Shon; G. Lee; S.-K. Song; M. Lee; J. Han; D. Lee (Journal of Atmospheric Chemistry, 2007)

Aggression and dominance in matched groups of subadult Icelandic horses (Equus caballus) - Hilde Vervaecke; Jeroen M. G. Stevens; Harold Vandemoortele; Hrefna Sigurjónsdóttir; Han De Vries (Journal of Ethology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Mammary tumor modifiers in BALB/cJ mice heterozygous for p53 - Joanna G. Koch; Xiangjun Gu; Younghun Han; Adel K. El-Naggar; Melissa V. Olson; Daniel Medina; D. Joseph Jerry; Anneke C. Blackburn; Gary Peltz; Christopher I. Amos; Guillermina Lozano (Mammalian Genome, 2007)

Cuticular wax biosynthesis in petunia petals: cloning and characterization of an alcohol-acyltransferase that synthesizes wax-esters - Andrew King; Jeong-Won Nam; Jixiang Han; Josh Hilliard; Jan G. Jaworski (Planta, 2007)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Soil Nitrification and Denitrification Potentials in a Wheat Field Soil as Affected by Elevated Atmospheric CO2 and Rice Straw Incorporation - Y. Shi; S. Y. Wang; L. Han; J. Yue; L. X. Yang; Y. L. Wang; J. G. Zhu (Bulletin of Environmental Contamination and Toxicology, 2006)

Cloning of ATP‐dependent protease ClpXP genes in Aeromonas veronii - H‐J Han; H Kondo; G Vivekanandhan; I Hirono; T Aoki (Journal of Fish Diseases, 2006)

Social structures in Pan paniscus: testing the female bonding hypothesis - Jeroen M. G. Stevens; Hilde Vervaecke; Han De Vries; Linda Van Elsacker (Primates, 2006)

Herbivore impact on grassland plant diversity depends on habitat productivity and herbivore size - Elisabeth S. Bakker; Mark E. Ritchie; Han Olff; Daniel G. Milchunas; Johannes M. H. Knops (Ecology Letters, 2006)
Mammalian herbivores can have pronounced effects on plant diversity but are currently declining in many productive ecosystems through direct extirpation, habitat loss and fragmentation, while being simultaneously introduced as livestock in other, often unproductive, ecosystems that lacked such species during recent evolutionary times. The biodiversity consequences of these changes are still poorly understood. We experimentally separated the effects of primary productivity and herbivores of different body size on plant species richness across a 10‐fold productivity gradient using a 7‐year field experiment at seven grassland sites in North America and Europe. We show that assemblages including large herbivores increased plant diversity at higher productivity but decreased diversity at low productivity, while small herbivores did not have consistent effects along the productivity gradient. The recognition of these large‐scale, cross‐site patterns in herbivore effects is important for the development of appropriate biodiversity conservation strategies.

Genetic diversity of avian infectious bronchitis coronavirus strains isolated in China between 1995 and 2004 - S. W. Liu; Q. X. Zhang; J. D. Chen; Z. X. Han; X. Liu; L. Feng; Y. H. Shao; J. G. Rong; X. G. Kong; G. Z. Tong (Archives of Virology, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

To the article “Tissue-specific changes in heme oxygenase activity and level of nonprotein Thiols in C57Bl/6 mice after whole-body γ-irradiation”, Vol. 140, No. 3, pp. 341–344 (2005) - Ensu Han; A. G. Platonov; M. Ya. Akhalaya; Ji Yon Son; Ji Yon An; Yon Suk Yun (Bulletin of Experimental Biology and Medicine, 2005)

Tissue-Specific Changes in Heme Oxygenase Activity and Level of Nonprotein Thiols in C57Bl/6 Mice after Whole-Body γ-Irradiation - Ensu Han; A. G. Platonov; M. Ya. Akhalaya; Ji Yon Son; Ji Yon An; Yon Suk Yun (Bulletin of Experimental Biology and Medicine, 2005)

Agrobacterium-mediated transformation of bottle gourd (Lagenaria siceraria Standl.) - J.-S. Han; C. K. Kim; S. H. Park; K. D. Hirschi; I.- G. Mok (Plant Cell Reports, 2005)

Efficient plant regeneration from cotyledon explants of bottle gourd (Lagenaria siceraria Standl.) - J-S. Han; D-G. Oh; I-G. Mok; H-G. Park; C. K. Kim (Plant Cell Reports, 2004)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Genetic mapping of EST-derived microsatellites from the diploid Gossypium arboreum in allotetraploid cotton - Z.-G. Han; W.-Z. Guo; X.-L. Song; T.-Z. Zhang (Molecular Genetics and Genomics, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Experimental investigation of the mammary gland tumour phantom for multifrequency microwave radio-thermometers - J. W. Lee; S. M. Lee; K. S. Kim; W. T. Han; G. Yoon; L. A. Pasmanik; I. A. Ulyanichev; A. V. Troitsky (Medical & Biological Engineering & Computing, 2004)

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Activation of a rice endogenous retrotransposon Tos17 in tissue culture is accompanied by cytosine demethylation and causes heritable alteration in methylation pattern of flanking genomic regions - Z. L. Liu; F. P. Han; M. Tan; X. H. Shan; Y. Z. Dong; X. Z. Wang; G. Fedak; S. Hao; Bao Liu (Theoretical and Applied Genetics, 2004)

Block Estimating of Spatial Yield Data and its Uncertainty - Shufeng Han; Sally M. Schneider; Robert G. Evans; Joan R. Davenport (Precision Agriculture, 2004)

p16 Expression in Squamous Lesions of the Female Genital Tract - Mary M. Finegan; Aaron C. Han; Mitchell I. Edelson; Norman G. Rosenblum (Journal of Molecular Histology, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Novel types of mutation in the choroideremia (CHM) gene: a full-length L1 insertion and an intronic mutation activating a cryptic exon - José A. J. M. van den Hurk; Dorien J. R. van de Pol; Bernd Wissinger; Marc A. van Driel; Lies H. Hoefsloot; Ilse J. de Wijs; L. Ingeborgh van den Born; John R. Heckenlively; Han G. Brunner; Eberhart Zrenner; Hans-Hilger Ropers; Frans P. M. Cremers (Human Genetics, 2003)

Recognition and implication of tectonic loading-induced reheating in the northern Variscan front (Belgium and northern France), based on an illite Kbler index and oxygen isotope study - G. Han; J. Yans; M. Goudalier; F. Lacquement; R. M. Corfield; J. L. Mansy; F. Boulvain; A. Prat (International Journal of Earth Sciences, 2003)

Effect of Nonylphenol on Apoptosis of Sertoli Cells in Vitro - X. Wang; X. Han; Y. Hou; G. Yao; Y. Wang (Bulletin of Environmental Contamination and Toxicology, 2003)

Pathogenicity and vaccine efficacy of a thymidine kinase gene deleted infectious laryngotracheitis virus expressing the green fluorescent protein gene - M. G. Han; C. H. Kweon; I. P. Mo; S. J. Kim (Archives of Virology, 2002)

Mutations in PATCHED-1, the receptor for SONIC HEDGEHOG, are associated with holoprosencephaly - Jeffrey E. Ming; Michelle E. Kaupas; Erich Roessler; Han G. Brunner; Mahin Golabi; Mustafa Tekin; Robert F. Stratton; Eva Sujansky; Sherri J. Bale; Maximilian Muenke (Human Genetics, 2002)

Allocation in recycling systems - Joost G. Vogtländer; Han C. Brezet; Charles F. Hendriks (The International Journal of Life Cycle Assessment, 2001)

Physical and Chemical Properties of a Winter-Time Yellow Sand Event in Northeast Asia - B. G. Kim; J. Y. Ahn; H. R. Noh; C. J. Park; J. S. Han; S. U. Park (Water, Air, & Soil Pollution, 2001)

A 15-year physical activity pattern is positively related to aerobic fitness in young males and females (13-27 years) - Han C.G. Kemper; Jos W.R. Twisk; Lando L.J. Koppes; Willem van Mechelen; G. Bertheke Post (European Journal of Applied Physiology, 2001)

The virtual eco-costs ‘99 A single LCA-based indicator for sustainability and the eco-costs-value ratio (EVR) model for economic allocation - Joost G. Vogtländer; Han C. Brezet; Charles F. Hendriks (The International Journal of Life Cycle Assessment, 2001)

Nitrogen in percolation water in paddy fields with a rice/wheat rotation - J.G. Zhu; Y. Han; G. Liu; Y.L. Zhang; X.H. Shao (Nutrient Cycling in Agroecosystems, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

Mechanism of dithionite reduction of the R2 protein of E. coli and mouse ribonucleotide reductase: evidence for reduction of FeIII 2 prior to the tyrosyl radical - A. Mark Dobbing; Joo-Yeon Han; A. G. Sykes (JBIC Journal of Biological Inorganic Chemistry, 1998)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

Enhanced salidroside production in liquid-cultivated compact callus aggregates of Rhodiola sachalinensis: manipulation of plant growth regulators and sucrose - J. F. Xu; P. Q. Ying; A. M. Han; Z. G. Su (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)

Strategies for the improvement of salidroside production in cell suspension cultures of Rhodiola sachalinensis - J. F. Xu; C. B. Liu; A. M. Han; P. S. Feng; Z. G. Su (Plant Cell Reports, 1998)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

The longitudinal development of running economy in males and females aged between 13 and 27 years: The Amsterdam Growth and Health Study - Geertje A. M. Arins; Willem van Mechelen; Han C. G. Kemper; Jos W. R. Twisk; Willem van Mechelen (European Journal of Applied Physiology, 1997)

Kinetic studies on the reduction of the R2 subunit of mouse ribonucleotide reductase with hydroxyurea, hydrazine, phenylhydrazine and hydroxylamine - Joo-Yeon Han; Astrid Gräslund; Lars Thelander; A. G. Sykes (JBIC Journal of Biological Inorganic Chemistry, 1997)

210 Pb-derived sediment accumulation rates in the southwestern East Sea (Sea of Japan) - G. H. Hong; S. H. Kim; C. S. Chung; D.-J. Kang; D.-H. Shin; H. J. Lee; S.-J. Han (Geo-Marine Letters, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Human Papillomavirus is More Prevalent in First Trimester Spontaneously Aborted Products of Conception Compared to Elective Specimens - P L Hermonat; L Han; P J Wendel; J G Quirk; S Stern; C L Lowery; T M Rechtin (Virus Genes, 1997)

Insoluble hydrophobin complexes in the walls of Schizophyllum commune and other filamentous fungi - Onno M. H. de Vries; M. Peter Fekkes; Han A. B. Wösten; Joseph G. H. Wessels (Archives of Microbiology, 1993)